Comparative Evaluation of Calcium Chloride and Polyethylene Glycol 400 on Drug Loading in Human Plasma-Derived Exosomes: Insights from BCS class II drug Spironolactone - Laraib Khan; Rabia Gul; Muhammad Sarfraz; Hamid Bashir; Nabi Shah; Nadeem Ahmad; Hafiz Rashid Hussain; Sabeeh Mohsin; Izna Khan; Yasser Shahzad; Imran Nazir; Muhammad Imran Amirzada (Journal of Pharmaceutical Innovation, 2027)

Structural dynamics and stability analysis of a novel ARSK variant confirms its role in MPS type X pathogenesis - Muhammad Bilal; Muhammad Fakhar; Thamir Eid; Nawal Helmi; Misbahuddin Rafeeq; Mehreen Gul; Hammal Khan; Muhammad Umair (Glycoconjugate Journal, 2026)

Moderate maize canopy defoliation improves light distribution, crop yields, and soybean seed quality in additive maize-soybean intercropping - Muhammad Ali Raza; Wang Zhiqi; Amjad Saeed; Hina Gul; Hassan Shehryar Yasin; Asif Naveed Ranjha; Zaheer Ahmed; Ghulam Raza; Wopke Van Der Werf; Akash Fatima; Xue Liang; Muhammad Hayder Bin Khalid; et al. (Field Crops Research, 2026)

Facile synthesis of cobalt-iron layered double hydroxide and its derived mixed metal oxide for Congo red and Pb(II) remediation - Ramzan Akhtar; Adil Khan; Maria Gul; Mohsin Ali Raza Anjum; Iqra Rafique; Muhammad Rehan; Rashid Nazir Qureshi; Sajid Iqbal; Muhammad Saifullah (Colloids and Surfaces C: Environmental Aspects, 2026)

Oxygen Containing Groups Modified Phosphate Rock for Pb(II) Adsorption - Shi-Yu Dong; Yang-Hao Zhao; Imran Muhammad; Gul Mehtab; Tie-Zhen Ren (Water, Air, & Soil Pollution, 2026)

Mitigation of aflatoxin B1-induced toxicopathology and immunosuppression in broilers using a multimodal antioxidant formulation - Muhammad Asad Ali; Muhammad Abdullah Arshad; Aisha Khatoon; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Muhammad Umar Ijaz; Sadaf Faiz; Aneela Amin (Mycotoxin Research, 2026)

Artificial intelligence-driven metallogenic typing of pyrite from global ore systems - Muhammad Amar Gul; Asia Kanwal; Mohamed Faisal; Tehseen Zafar; Rizwan Sarwar Awan; Shamim Akhtar; Ibrar Khan; Xiaoyong Yang (Journal of Geochemical Exploration, 2026)

Development and Characterization of Exosomes Mediated Transdermal Gel for Enhanced Delivery of Hydroxyurea - Wajeeha Khalid; Rabia Gul; Muhammad Sarfraz; Hamid Bashir; Nadeem Ahmad; Nayab Tahir; Aneela Javed; Muhammad Asad; Ahsan Ibrahim; Aamra Imtiaz; Imran Nazir; Muhammad Imran Amirzada (Journal of Pharmaceutical Innovation, 2026)

Fertilizing Effect of Codium flabellatum and Aspergillus japonicus (Algal-Fungal) Nexus Improves Growth, Nutrient Fluxes and Fruit Quality in Brassica napus in Saline Condition - Ayesha; Humaira Gul; Mamoona Rauf; Asma Tabassum; Aliya Rehman; Muhammad Arif; Muhammad Hamayun; Mohamed A. El-Sheikh; Zainul Abideen (Journal of Soil Science and Plant Nutrition, 2026)

Microbe-mediated drought stress alleviation: Fusarium verticillioides enhances maize growth by upregulation of physiological, biochemical, and molecular responses - Raid Ali; Humaira Gul; Mamoona Rauf; Sajid Ali; Muhammad Arif; Sumera Afzal Khan; Anwar Hussain; Bokyung Lee; Muhammad Hamayun (South African Journal of Botany, 2026)

Time-domain stochastic fracture analysis of soil-structure interaction systems using a high-order stochastic Galerkin SBFEM - Muhammad Gul; Chengbin Du; Wei Wang (Computers and Geotechnics, 2026)

AI and Multi-Omics for Climate-Resilient Remediation of Heavy Metal Soil Toxicity - Isma Gul; Muhammad Adil; Siqi Lu; Safdar Bashir; Heli Lu; Muhammad Daud; Younas Iqbal; Yu Tao (Water, Air, & Soil Pollution, 2026)

Assessment of functional trait variation in arid-zone plant families to evaluate indicator species for rehabilitation of degraded landscapes - Eisha Kanwal; Farooq Ahmad; Ansa Asghar; Ummar Iqbal; Anum Javaid; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Saba Gul; Muhammad Irshad; Khawaja Shafique Ahmad (The Science of Nature, 2026)

Pollen micromorphological variations in selected species of genus Ipomoea (Convolvulaceae) and their taxonomic significance - Aleena Gul; Muhammad Zafar; Salman Majeed; Muhammad Rizwan Khan; Samah A. Alharbi; Sayyara Ibadullayeva; Shomaila Ashfaq; Khuzin Dinislam; Adnan Amin; Samira Khudaverdiyeva (Plant Biosystems, 2026)

Multi-trait plant growth-promoting endophytic fusarium proliferatum from phoenix dactylifera enhanced wheat growth under drought stress condition - Salman Khan; Khalil Ur Rahman; Nida Karishma; Mamoona Rauf; Humaira Gul; Muhammad Hamayun; Abdulwahed Fahad Alrefaei; Faheem Anwar; Sajid Ali; Muhammad Arif (Acta Physiologiae Plantarum, 2026)

Artificial intelligence for climate change mitigation and adaptation: A domain-structured review of methods, applications, and research gaps for seven high-impact domains - L. Minh Dang; Sufyan Danish; Muhammad Fayaz; Gul E. Arzu; Andy Nguyen; Hyoung-Kyu Song; Hyeonjoon Moon (Process Safety and Environmental Protection, 2026)

Biocontrol of powdery mildew in luffa by the silicon-solubilizing endophytic fungi from Trichoderma koningii and Aspergillus clavatus - Asim Ur-Rahman; Sundus Rauf; Khalil Ur Rahman; Mamoona Rauf; Humaira Gul; Alaa Baazeem; Mohamed M. Hassan; Muhammad Hamayun; Muhammad Arif (Physiological and Molecular Plant Pathology, 2026)

Nanotechnology for Climate-Resilient Agriculture: Advancing Water Efficiency, Crop Resilience, and Sustainable Food Security - Muhammad Adil; Isma Gul; Siqi Lu; Heli Lu; Yu Tao (Water, Air, & Soil Pollution, 2026)

Desert treasures: a comprehensive review of the diversity, phytochemistry, ethnobotany, and conservation of thar desert flora - Ummar Iqbal; Hafiza Zahra Naseem; Hadia Jabeen; Muhammad Faraz Gul; Saba Gul; Nargis Naz; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf (The Science of Nature, 2026)

Zaleya pentandra L. produces anti-arthritic effects by downregulating IL-6, NF-κB, and TNF-α and mitigating oxidative stress - Ayesha Shafi; Naureen Shehzadi; Khalid Hussain; Muhammad Saleem; Fatima Rasool; Mubashara Gul (Inflammopharmacology, 2026)

Integrating crowdsourced geospatial intelligence and urban morphology for urban waterlogging risk mapping in Karachi, Pakistan - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Yinghai Li; Chengshuai Liu; Junaid Abdul Wahid; Jiali Guo; Xiaotao Shi; Gul-e-Zehra Soomro (Climatic Change, 2026)

Cortinarius squamibrunneus sp. nov. ( Basidiomycota ; Agaricales ) in C . Section Safranopedes of Subgenus Telamonia from Swat District, Khyber Pakhtunkhwa, Pakistan - Hira Ijaz; Tasneem Ashraf; Muhammad Naveed; Gul Sanga; Sadiq Ullah; Sana Jabeen (New Zealand Journal of Botany, 2026)
Cortinarius squamibrunneus sp. nov. was collected from Swat District, Khyber Pakhtunkhwa, Pakistan. The species is distinguished from its closely related species, C . epipurrus , by its pale orangish‐brown to brown, fibrillose–squamulose pileus with a darker central disc and a rimose to radially cracked margin, smaller basidiospores (5.5–7.4 × 3.6–5 μm) with finely ornamented warts and variably shaped sterile cells. Comparative morphological analyses combined with molecular phylogenetic inference based on the ITS region of nrDNA confirm that this taxon is distinct from previously described species and represents a new species within C. sect. Safranopedes of C . subg. Telamonia .

Essential oils: A promising eco-friendly and sustainable approach for effectively managing all life stages of insect pests-A review - Mirza Gul; Muhammad Zahid; Hazrat Ali (International Journal of Tropical Insect Science, 2026)

Genomic insights into phage SGP007 reveal a potent therapeutic candidate for targeted control of salmonellosis in poultry - Sidra Tul Muntaha; Gul Nabi Khan; Ibrar Khan; Muhammad Hassan; Iqbal Ahmed Alvi; Tawaf Ali Shah; Gehan M. Elossaily; Turki M. Dawoud (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Validating the Efficiency of the AquaCrop Model Under Full and Deficit Irrigation Regimes to Simulate Future Climate Impacts on Wheat Crop - Shamim Ara Memon; Irfan Ahmed Shaikh; Mashooque Ali Talpur; Abdul Rahim Junejo; Munir Ahmed Mangrio; Nazar Gul; Zaheer Ahmed Khan; Hafiz Abdul Salam; Muhammad Ashraf (Irrigation and Drainage, 2026)
Wheat yield and water demand are affected by the ongoing disturbance of climatic factors and greenhouse gases (GHG). As a result, the AquaCrop model's ability to anticipate climate change impacts on wheat harvests under full and deficit irrigation regimes in Sindh, Pakistan, was evaluated using wheat trials conducted between 2018 and 2020. However, for its validation, the results of the deficit irrigation treatment ITS 50 (50% controlled irrigation at the tillering stage) for both seasons were employed. The model efficiently estimated yield with a normalised root‐mean‐square error (NRMSE) of 13% and 17%, a Willmott's d ‐index of 98% and a Nash–Sutcliffe efficiency (NME) of 95% under full and deficit irrigation treatments, respectively. The simulation results revealed an adverse effect of climate change on the yield and water productivity of wheat. Over the century, the model predicted an increase of 6% to 7% in wheat yield under full (well‐watered) irrigation and a decrease of 10 to 12% in 25% reduced water applied depth (RAD) and 21% to 24% under 50% RAD scenarios for both representative concentration pathway RCPs (4.5 and 8.5). The overall wheat water productivity increased under a well‐watered irrigation regime by 16% in RCP8.5 compared with RCP4.5.

Corrigendum to “Underground geological sequestration of carbon dioxide (CO2) and its effect on possible enhanced gas and oil recovery in a fractured reservoir of Eastern Potwar Basin, Pakistan” [Sci. Total Environ. 905 (2023) 167124] - Anaiz Gul Fareed; Fabio De Felice; Antonella Petrillo; Muhammad Arsalan Sultan; Zafar Khan Jalalzai (Science of The Total Environment, 2026)

Sustainable valorization of olive pomace industrial side stream via explainable machine learning guided biochar pyrolysis - Muhammad Ali Haider; Jawad Gul; Muhammad Nouman Aslam Khan; Dagmar Juchelkova (Process Safety and Environmental Protection, 2026)

Social media sentiment exposure to climate-induced floods and risk responses to the 2022 flood in Pakistan - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Nishan-E-Hyder Soomro; Jiali Guo; Caihong Hu; Muhammad Faisal; Junaid Abdul Wahid; Gul-e-Zehra Soomro (Journal of Environmental Management, 2026)

Quality assessment and authenticity evaluation of honey samples from local traders in Peshawar, Pakistan - Abdul Wahab; Muhammad Younus; Shehla Begum; Wahid Gul (Environmental Monitoring and Assessment, 2026)

Insecticidal activity against mosquito larvae, leishmanicidal activity, and cytotoxicity against human cells of a synthesized thiourea compound and a column chromatography fraction (AF5) from the n-hexane soluble fraction of Artemisia scoparia - Mirza Gul; Muhammad Zahid; Hazrat Ali; Muhammad Said; Sajjad Ahmad (Journal of Asia-Pacific Entomology, 2026)

Carboxylated Graphene Oxide (CGO) Adsorbent as an Effective and Green Approach for Targeting As (III) with Improved Adsorption Characteristics - Khizar Hussain Shah; Gul Afshan Khan; Zaher Hashisho; Sadaf Sarfraz; Muhammad Fahad; Muhammad Kazim (Water, Air, & Soil Pollution, 2026)

Is Critical Period for Weed Control Influenced by the Application of Pre-emergence Herbicide in Lentil (Lens culinaris Medik.)? - Muhammad Zia Ul Haq; Anas Ali; Gul Zaib Hassan; Rana Nadeem Abbas; Saira Shafiq; Mubashar Nadeem (International Journal of Plant Production, 2026)

Genome-wide identification and expression analysis of YTH gene family in barley reveals their potential role under abiotic stresses - Muhammad Mudasir; Muhammad Shahzad; Ayesha Bibi; Shareef Gul; Liu Qiuyi; Sarmad Frogh Arshad; Hameed Gul; Ali Shahzad (Genetica, 2026)

Synthesis of quinoline-pyridazinone hybrid molecules by using a bio-based aldo-X building block DMEMPO from levulinic acid - Muhammad Noman Haider Tariq; Gul Khanda Sajjad; Tianjian Zhang; Rongxian Bai; Babak Kaboudin; Yanlong Gu (Sustainable Chemistry and Pharmacy, 2026)

Betaine-loaded Foeniculum vulgare@Fe-MOF: A novel approach to combat bleomycin-induced hepatotoxicity in rats - Sana Batool; Iftikhar Ahmed; Calvyn Howells; Li Haitao; Muhammad Saqib Saif; Tuba Tariq; Riaz Hussain; Muhammad Mahmood Ahmad; Sobia Tauheed; Chaokun Hong; Tauseef Munawar; Shahbaz Gul Hassan; et al. (Journal of Environmental Chemical Engineering, 2026)

Aspergillus flavus and Colpomina sinousa mixture act as biocatalyst to improve growth, fruit yield and salinity resistance of Brassica napus for sustainable agriculture - Hira Wahid; Humaira Gul; Mamoona Rauf; Asma Tabassum; Aliya Rehman; Muhammad Arif; Muhammad Hamayun; Hatem E. Semary; Zainul Abideen (Biocatalysis and Agricultural Biotechnology, 2026)

Synergistic Effects of Multi-walled Carbon Nanotubes and Plant Growth Regulators on In Vitro Morphogenesis of Sugarcane (Saccharum spp. L.) - Aneela Iqbal; Raham Sher Khan; Karim Gul; Muhammad Aizaz; Mohammad Tahir; Hazir Rahman; Douglas Law; Ayaz Ahmad (Sugar Tech, 2026)

Enhancing Lodging Resistance in Rapeseed Strategies for Sustainable Agriculture and Yield Improvement - Shahid Ullah Khan; Umer Mahmood; Muhammad Sirab Khan; Minchao Qian; Shengting Li; Osama Alam; Yonghai Fan; Hui Wang; Wei Chang; Hameed Gul; Shah Fahad; Kun Lu (Journal of Plant Growth Regulation, 2026)

Thal desert flora: diversity, abundance, phytochemistry, therapeutic potential, and conservation status - Ummar Iqbal; Muhammad Faraz Gul; Zahra Naseem; Hadia Jabeen; Mansoor Hameed; Nargis Naz; Farooq Ahmad (Genetic Resources and Crop Evolution, 2026)

Genetically Encoded Near-Infrared Fluorescent Proteins for Viral Imaging and Detection: A Mini-Review - Fakhrul Hassan; Abbas Khan; Muhammad Suleman; Faez Iqbal Khan; Ijaz Gul (Current Microbiology, 2026)

Metagenomic Exploration of the Bacteriome Reveals Natural Wolbachia Infections in Yellow Fever Mosquito Aedes aegypti and Asian Tiger Mosquito Aedes albopictus - Gul E. Nayab; Rafi ur Rahman; Fazal Hanan; Inamullah Khan; Muhammad Fahim (Current Microbiology, 2026)

Caffeoylquinic acid derivatives isolated from Tussilago farfara L. as potential anti-leishmanial agents; in vitro and in silico studies - Izaz Ahmad; Salar Hafez-Ghoran; Muhammad Yousuf; Humaira Zafar; Atia-tul- Wahab; Sammer Yousuf; Mushtaq Ahmad; Inam Gul; Bates Kudaibergenova; M. Iqbal Choudhary (Natural Product Research, 2026)

Machine learning-guided discovery of mitogen-activated protein kinase 7 (MAPK7 inhibitors): integrating virtual screening, docking, and molecular dynamics simulations - Chandni Hayat; Amar Ajmal; Nayab Gul; Muhammad Numan; Haleema Bibi; Naveed Akhtar; Laiba Sultan; Arif Ali; Muhammad Tahir Khan; Muhammad Saqib (In Silico Pharmacology, 2026)

Impact of Aspergillus flavus infection on nutrient composition and storage quality of maize (Zea mays L.) using side needle inoculation - Imran Manzoor; Muhammad Arshad; Rao Muhammad Samran Gul; Ijaz Rasool Noorka; Momina Hussain; Muhammad Sajid; Noorah A. AlKubaisi; Sezai Ercisli; Mohamed S. Elshikh; Abdul Waheed (Journal of Stored Products Research, 2026)

Small-sized fixed domain monitoring underwater profiler: A multi-factor comparative analysis - Yang Zhang; Xin Zhang; Qingchao Xia; Canjun Yang; Ruiyin Song; Dingze Wu; Rui Zhou; Jiayu Hou; Gul Muhammad (Ocean Engineering, 2025)

Air quality management from the lens of leveraging social media data and machine learning algorithm for hazard zoning-real-time air pollution detection in urban cities under changing climate - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Nishan-E-Hyder Soomro; Gul-e-Zehra Soomro; Muhammad Faisal; Caihong Hu; Junaid Abdul Wahid; Jiali Guo (Journal of Environmental Management, 2025)

Biomonitoring Vehicular Pollution Using Naturally Occurring Indicator Species Ricinus communis L. (Euphorbiaceae) Along Roadways - Muhammad Faisal Gul; Ummar Iqbal; Muhammad Sharif; Nargis Naz; Farooq Ahmad (Water, Air, & Soil Pollution, 2025)

Advances in Microbial Bioremediation of Microplastics in Mangrove Sediments: a Comprehensive Review - Muhammad Sheeraz Javed; Muhammad Adil; Jiliang Zhang; Isma Gul; Muhammad Rauf; Saeed Ahmad; Bushra Moon; Siqi Lu; Heli Lu; Ali Haidar Gormani; Younas Iqbal; Hassan Mahmood (Water, Air, & Soil Pollution, 2025)

Smart and Sustainable Microplastic Removal: Hybrid Systems, Bio-Inspired Technologies, Real-Time Sensing, and Policy Integration - Salman khan; Umme Kalsoom; Muhammad Kashif; Syed Aamir Hussain; Misbah Gul; Shohreh Azizi; Malik Maaza (Water, Air, & Soil Pollution, 2025)
The pervasive accumulation of microplastics in aquatic ecosystems has emerged as a critical global environmental challenge with profound implications for biodiversity, food safety, and human health. Conventional remediation approaches often fail to address microplastics' complex physiochemical diversity and resilience. In recent years, hybrid and bio-inspired technologies have emerged as promising alternatives for efficient microplastic remediation. This review critically examines the state-of-the-art hybrid systems comprising synergetic combinations of physical, chemical, and biological processes and bio-inspired approaches that mimic natural filtration, adhesion, and degradation mechanisms. Emphasis is placed on membrane-based hybrids, nature-mimicking adsorbents, and enzyme-functionalized materials and microrobots, as well as recent advances in smart monitoring systems and sensor technologies for real-time detection. Additionally, the review highlights the importance of integrated policies and technological synergies, stressing the need for harmonized regulatory frameworks and cross-sector collaboration to enable scalable and sustainable solutions. By integrating interdisciplinary insights, this work positions hybrid, bio-inspired and data-informed strategies at the forefront of sustainable solutions for microplastic remediation, paving the way toward cleaner ecosystems and circular plastic economies.

Evaluation of hepatic cancer stem cells (CD73+, CD44+, and CD90+) induced by diethylnitrosamine in male rats and treatment with biologically synthesized silver nanoparticles - Amber Pervez; Behramand Khan; Gul Nabi Khan; Sumayya Khattak; Mazhar Ali; Komal Mujeeb; Bushra Nasib; Hyung Goo Kim; Irfan Zia Qureshi; Muhammad Arshad (Molecular Biology Reports, 2025)

Improving Nitrogen Efficiency and Photosynthesis in Wheat Using integrated Nitrogen Management and Modified Geometry - Uzair Ahmed; Muhammad Waseem Abbas; Jalal Bayar; Irshad Ali Khan; Aneela Tahmeed; Muhammad Mehran Anjum; Nawab Ali; Gul Roz Khan; Hazrat Usman; Mahmoud F. Seleiman (Journal of Soil Science and Plant Nutrition, 2025)

Halotolerant Bacillus Aryabhattai Strain PM34 Mitigates Salinity Stress and Enhances the Physiology and Growth of Maize - Muhammad Atif Azeem; Salman Khan; Fawad Ali; Sajjad Ahmad; Gul Rahim; Muhammad Iftikhar; Majid Iqbal; Rawa Saad Aljaloud; Khaloud Mohammed Alarjani; Hassan Javed Chaudhary (Journal of Plant Growth Regulation, 2025)

Morpho-molecular diversity and host range dynamics of squash powdery mildew pathogens prevailing in Pothwar Plateau, Pakistan - Beenish Gul; Farah Naz; Mathews L. Paret; Fanny Iriarte; Zain Haider; Gulshan Irshad; Muhammad Azam Khan (Journal of Plant Pathology, 2025)

Tea (Camellia sinensis L.) anthocyanins and their compounded stability through conjugation: A promising instrument to synthesize green, halochromic, active and intelligent packaging - Muhammad Safiullah Virk; Muhammad Abdulrehman Virk; Mehak Gul; Shiyu Zhang; Tabussam Tufail; Xinzhuan Yao; Litang Lu (Trends in Food Science & Technology, 2025)

Long-term impacts of agronomic practices on winter wheat yield, water use efficiency, and nitrogen use efficiency in global dryland regions: A meta-analysis - Muhammad Adil; Zhenchuang Wang; Yi Chen; Heli Lu; Siqi Lu; Safdar Bashir; Isma Gul; Huan Li; Zongran Han; Wanfu Feng (Soil and Tillage Research, 2025)

Effect of Ocimum tenuiflorum L. compounds on Oreochromis mossambicus: a combination of molecular docking, biochemical dynamics, and antifertility assessment - Sajida Afzal; Siraj Khan; Muhammad Nauman Khan; Zahida Nasreen; Hansa Gul; Mian Inam Zaib; Hameed Alsamadany; Khalid H. Alamer; Ibtisam M. Alsudays; Muhammad Tahir Naseem (Aquaculture International, 2025)

Paleoenvironmental conditions and key drivers of organic matter accumulation in the early cretaceous Talhar Shale, Lower Indus Basin, Pakistan - Rizwan Sarwar Awan; Bo Liu; Qamar Yasin; David A. Wood; Hamad ur Rahim; Muhammad Amar Gul; Sajjad Ali; Khawaja Hasnain Iltaf; Ashar Khan (Journal of Asian Earth Sciences, 2025)

A comprehensive assessment of heavy metal pollution in flood-affected areas in Pakistan: a case study of the 2022 superflood through pollution and water quality indices - Nida Gul; Nazish Huma Khan; Nasir Mehmood; Muhammad Idrees; Carlos A. T. Toloza; Eman Alzahrani; Rachel Ann Hauser-Davis; Sarzamin Khan (Sustainable Water Resources Management, 2025)

Correction: Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Levilactobacillus brevis MW362790 and Pediococcus pentosaceus MT323062 Alleviate Cadmium-Induced Oxidative Stress and Hepato-renal Toxicity - Mamoona Hameed; Saman Javed; Najma Arshad; Zaman Gul; Maria Mushtaq; Aneela Munir; Kiran Shazadi; Muhammad Arshad; Saleha Noureen (Current Microbiology, 2025)

Uncovering the oxidative stress and hematological consequences of chronic cobalt exposure on atherosclerosis - Rashad Ibragimov; Rovshan Khalilov; Fidan Nuriyeva; Ilgiz Gareev; Ozal Beylerli; Sergey Roumiantsev; Muhammad Zafar; Deema Kamal Sabir; Salman Majeed; Muhammad Rizwan Khan; Aleena Gul; Jonida Biturku (BioMetals, 2025)

Maize/Legume Intercropping Increases Nutrient Uptake, Crop Yields, Land Productivity, and Economic Profits in Resource-intensive Arid-irrigated Areas - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Ghulam Abbas Shah; Wang Zhiqi; Muhammad Jawad Hassan; Muhammad Bilal; Harun Gitari; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Fertilizing Effects of Ulva intestinalis Derived Bio-Stimulant Enhance Spinacea oleracea L. Production, Nutrient Fluxes and Secondary Metabolism Under NaCl Stress - Sadaf Gul; Hamad Aslam; Muhammad Farrakh Nawaz; Ghulam Yasin; Sana Riaz; Maria Hasnain; Mohamed A. El-Sheikh; Emanuele Radicetti; Zainul Abideen (Journal of Soil Science and Plant Nutrition, 2025)

Molecular characterization of lumpy skin disease virus in the cattle population of District Lower Chitral, Khyber Pakhtunkhwa, Pakistan - Almas Faryal Nizam; Iram Maqsood; Hanif Ur Rahman; Saira Awaz; Imran Ullah Shah; Muhammad Ijaz Ali; Baitullah Khan; Gul Muhammad; Asima Azam; Ayesha Hidayat (Antonie van Leeuwenhoek, 2025)

Insecticide resistance in the filariasis vector Culex quinquefasciatus in Khyber Pakhtunkhwa, Pakistan: implications for mosquito control - Mirza Gul; Muhammad Zahid; Muhammad Zahoor (International Journal of Tropical Insect Science, 2025)

Isolation, biochemical characterization, and antimicrobial activities of EPS-producing bacterial endophytes from Moringa oleifera - Karim Gul; Raham Sher Khan; Aneela Iqbal; Atta Ullah; Syed Muhammad Shafi Shah; Anwar Hussain; Douglas Law; Ayaz Ahmad; Salimullah Khan (Folia Microbiologica, 2025)

Harnessing public sentiment discourse for early drought detection and water crisis response for strategic water management and resilient policy planning - Shan-e-hyder Soomro; Muhammad Waseem Boota; Nishan-E-hyder Soomro; Gul-e-Zehra Soomro; Jiali Guo; Caihong Hu; Junaid Abdul Wahid (Science of The Total Environment, 2025)

Unlocking paleolatitudinal secrets of the early Cretaceous by rare earth element imprints: Implications for seawater chemistry, depositional environments, and paleoclimate in the Talhar Shale, Lower Indus Basin, Pakistan - Rizwan Sarwar Awan; Bo Liu; Hongxia Li; Sajjad Ali; Muhammad Amar Gul; Lingsheng Zhao; Ashar Khan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Vanadium anchored 3D nanoconfined KIT-6 silica walls for fast oxidative desulfurization of fuel: A detailed thermodynamic and kinetic examination - Afaq Nazir; Safia Gul Lalayi; Jehangir Khan; Atif Ahmad; Chen Shu Huan; Muhammad Qamer Abbas; Zhenxia Du (Journal of Hazardous Materials, 2025)

Ore genesis and critical metal enrichment using deep learning algorithms in Gunga Pb-Zn deposit, Southern Pakistan: Constraints from sphalerite geochemistry and isotopic compositions - Muhammad A. Gul; Huishan Zhang; Yu Yang; Guangli Ren; Chao Sun; Xiaojian Zhao; Tahir Bin Yousuf; Ahmed Shah; Rizwan Sarwar Awan; Mohamed Faisal; Xiaoyong Yang (Journal of Geochemical Exploration, 2025)

Enhancing Salt Tolerance in Tomato Crop Using Microbial Inoculants - Farheen Islam; Afshan Rahman; Hafiza Farhat; Urooj Muhammad Sharif; Nawal Gul; Areeba Aslam (Journal of Crop Health, 2025)

Comparative Genetic Analysis of Triticum aestivum Varieties Under Salt Stress: Integrating Morphological and Biochemical Traits - Shareef Gul; Hameed Gul; Muhammad Mudasir; Maroof Fatima; Hesheng Yao; Ali Shahzad (Journal of Crop Health, 2025)

Palynological research and taxonomic implications of selected bee forage plants using microscopic techniques for accurate taxa identifications - Ateef Ullah; Mushtaq Ahmad; Naila Mukhtar; Shabir Ahmad; Hussain Shah; Faran Durrani; Huma Gul; Muhammad Abdullah; Nasira Bibi; Nabeel Ur Rehman; Reem M. Aljowaie; Abd El-Zaher M. A. Mustafa; et al. (Genetic Resources and Crop Evolution, 2025)

Combination of Sargassum wightii extract and pyridoxin mixture improves growth and salinity tolerance in Okra for sustainable agriculture - Zawar Khan; Humaira Gul; Aliya Rehman; Asma Tabassum; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Mohamed A. El-Sheikh; Zainul Abideen (Algal Research, 2025)

Comparative efficacy of imidocarb dipropionate with additive in naturally infected cattle against bovine babesiosis - Sajida Bibi; Sidra Abbas; Muhammad Arfan Zaman; Roquyya Gul; Aima Iram Batool; Iqra Khalil; Arbab Sikandar; Farhan Ahmad Atif (Veterinary Parasitology, 2025)

Geological and geochemical evolution of the Derhib sulfide-talc deposit in the South Eastern Desert, Egypt: Insights into ore genesis and metasomatic alteration - Mohamed Faisal; Huan Li; Rub'son N'nahano Heritier; Muhammad A. Gul; Farah A. Khedr; Zhekai Zhou; Sobhi M. Ghoneim (Lithos, 2025)

Cadmium Toxicity Affects Morpho-Physiological and Biochemical Attributes in Gladiolus grandiflorus L.: The Mitigating Roles of Exogenous Strigolactone (GR24) - Muhammad Ahsan; Muhammad Abdullah; Emanuele Radicetti; Mohamed Farouk Elsadek; Ali Bakhsh; Mateen Sajid; Mohammad Valipour; Aftab Jamal; Hera Gul; Syed Mohsin Abbas (Water, Air, & Soil Pollution, 2025)

Comparative efficacy of combined myo-inositol and D-chiro inositol versus metformin across PCOS Phenotypes: enhancing ovarian function, ovulation, and stress response in a prospective clinical trial - Meena Gul; Hina Khan; Bushra Rauf; Syed Murtaza Shah Bukhari; Ehtesham Ehtesham; Muhammad Omar Malik; Fawad Ali Shah; Fawaz E. Alanazi; Mohsin Shah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Preparation, Characterization and Removal of Acid Blue 129 and Erioglaucine Dyes from Aqueous Solution by Corn Cob Based Activated Carbon - Sultan Alam; Najeeb ur Rahman; Muhammad Ilyas; Iram --; AlSaba Gul; Muhammad Zahoor; Muhammad Naveed Umar; Riaz Ullah; Essam A. Ali (Bulletin of Environmental Contamination and Toxicology, 2025)

Overexpression of StDREB30 Gene Enhances Salt Stress Tolerance in Transgenic Potato - Qurat- Ul Ain-Ali; Faiza Munir; Muhammad Faraz Bhatti; Rabia Amir; Alvina Gul (Potato Research, 2025)

The Effects of miR-22-3p on Differentiation of Human Dental Pulp Stem Cells into Neural Progenitor-Like Cells - Muhammad Tehsil Gul; Muhammad Nasir Khan Khattak; Rizwan Qaisar; Manju Nidagodu Jayakumar; A. B. Rani Samsudin; Amir Ali Khan (Molecular Neurobiology, 2025)

Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Urban cities heatwaves vulnerability and societal responses towards hazard zoning: Social media real-time based heatwave detection using deep learning - Shan-e-hyder Soomro; Muhammad Waseem Boota; Gul-e-Zehra Soomro; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Yinghai Li; Jiali Guo; Junaid Abdul Wahid (Sustainable Cities and Society, 2025)

Phytomining potential, micro-morphological assessment, and air pollution tolerance index of plant species in multi-metals contaminated soapstone and crushing stone mines - Tufail Shakeel; Ghulam Mujtaba Shah; Bibi Saima Zeb; Iram Gul; Muhammad Irshad; Habiba Zafar (Science of The Total Environment, 2025)

Machine learning-driven classification of Pb Zn ore deposits using pyrite trace elements and isotopic signatures: A case study of the Gunga deposit - Muhammad Amar Gul; Huishan Zhang; Yanguang Li; Xiaoyong Yang; Chao Sun; Xiaojian Zhao; Guangli Ren; Asia Kanwal; Muhammad Hafeez; Yu Yang; Rizwan Sarwar Awan; Mohamed Faisal (Journal of Geochemical Exploration, 2025)

Exploring the potential of a pH-sensitive hydrogel sponge: interpenetrating network of tragacanth and pectin for controlled delivery of levosulpiride - Muhammad Umer Ashraf; Muhammad Awais Iqbal; Kashif Barkat; Irfan Anjum; Muhammad Naveed Mushtaq; Rabia Gul; Muhammad Aamir; Samir Ibenmoussa; Ahmad Mohammad Salamatullah; Mohammed Bourhia; Gamal A. Shazly; Gezahign Fentahun Wondmie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Role of polyphenolics in the management of rheumatoid arthritis through intracellular signaling pathways: a mechanistic review - Uzma Saleem; Maryam Farrukh; Malik Saadullah; Rida Siddique; Humaira Gul; Aqsa Ahmad; Bushra Shaukat; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Evaluation of genotoxicity and physicochemical variations of Eichhornia crassipes (Mart.) Solms exposed to paper-mill-contaminated wastewater - Harma Shah; Muhammad U. F. Awan; Zahid Mehmood; Noor Sana; Wasim Abbas; Adeel Ahmad; Abdullah Qasim; Annum Gul; Ali Hasnain; Hsi-Hsien Yang (Environmental Monitoring and Assessment, 2025)

Biomonitoring and phytoremediation potential of Conocarpus erectus (Buttonwood) for mitigating air pollution from highway traffic - Akkasha Azam; Ummar Iqbal; Zartasha Usman; Muhammad Sharif; Muhammad Faisal Gul; Nargis Naz; Ifrah Nawaz; Farooq Ahmad (Chemosphere, 2025)

Layer-by-layer concurrent encapsulation of probiotics and bioactive compounds with supplementation in intermediary layers: An establishing instrument for microbiome recharge, core safety, and targeted delivery - Muhammad Safiullah Virk; Muhammad Abdulrehman Virk; Mehak Gul; Muhammad Awais; Qiufang Liang; Tabussam Tufail; Mingming Zhong; Yufan Sun; Abdul Qayum; Ekram Abd El-Salam; John-Nelson Ekumah; Abdur Rehman; et al. (Food Hydrocolloids, 2025)

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

Maize cultivar mixtures: a sustainable approach for weed management under reduced herbicide dose - Amina Shahbaz; Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Amar Matloob; Rizwan Maqbool; Muhammad Tayyab Hanif; Muhammad Abu Bakar Hayat (Phytoparasitica, 2025)

Exploring the anti-diabetic properties of camel milk: effects on blood glucose, antioxidant defense, and organ histo-morphological features in rabbits - Muhammad Asif Arain; Gul Bahar Khaskheli; Ghulam Shabir Barham; Qurban Ali Shah; Fazul Nabi; Mikhlid H. Almutairi; Bader O. Almutairi; Illahi Bakhash Marghazani (Journal of Molecular Histology, 2025)

Genome wide and evolutionary analysis of ALOG gene family and its role during seed development and nodulation in response to rhizobium in soybean - Muhammad Zulfiqar Ahmad; Bushra Ahmad; Jamal Abdul Nasir; Arshad Jamil; Saqib Ali; Asma Gul; Abdullah A. Alarfaj; Sulaiman Ali Alharbi (Genetic Resources and Crop Evolution, 2025)

Theabrownin: a dietary nutraceutical with diverse anticancer mechanisms - Muhammad Faisal Maqbool; Sameena Gul; Muhammad Ishaq; Amara Maryam; Muhammad Khan; Hafiz Abdullah Shakir; Muhammad Irfan; Yongming Li; Tonghui Ma (Natural Product Research, 2025)

Do structural and functional traits modulation determine the ecological fate of castor bean (Ricinus communis L.) under variable pedospheric and atmospheric conditions? - Ummar Iqbal; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (South African Journal of Botany, 2025)

Integrated Weed Management in Sunflower Using a Hybrid Mixture and Reduced Herbicide Dose - Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Muhammad Shahid Ibni Zamir; Amina Shahbaz; Muhammad Saqib (Journal of Crop Health, 2025)

Toxicity and fitness evaluation of Chrysoperla carnea resistant strains on cotton mealy bug Phenacoccus solenopsis Tinsely - Mashahood Ali Khan; Sarfraz Ali Shad; Fehmina Atta; Muhammad Gul Zaman; Muhammad Abubakar (Crop Protection, 2025)

Elevation-dependent snow cover dynamics and associated topo-climate impacts in upper Indus River basin - Muhammad Farhan Ul Moazzam; Abhishek Banerjee; Ghani Rahman; Byung Gul Lee (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Electronic, thermoelectric and magnetic properties of ternary telluride KAlTe2 and KInTe2 from theoretical perspective - Zahid Ullah; Muhammad Amir; Aiman Bazilla; Salim Ullah; Umar Shahzad; Nazir Ullah; Jabir Khan; Sabahat Gul (Next Research, 2024)

Sustainable Development Goals (SDGs): The nexus of fintech and water productivity in 11 BRICS countries - Cem Işık; Jie Han; Wei Zhang; Anas Muhammad; Stefania Pinzon; Gul Jabeen (Journal of Environmental Management, 2024)

Kinetics of silver ion encapsulation as nanoparticles using Vaccinium oxycoccos plant extract for the efficient sensing of Cr(iii) ions and its biological assessment - Amna Bibi; Muhammad Iqbal Zaman; Abdul Niaz; Sania Bibi; Saba Gul; Naveed Ahmad; Hanan E. Osman (Chemical Engineering Journal, 2024)

Insights Into the Morphological Analysis, Phytochemical Profile and Antimicrobial Activities of the Multi-Walled Carbon Nanotubes-Induced In Vitro Sugarcane - Aneela Iqbal; Muhammad Usman; Karim Gul; Atta Ullah; Syed Muhammad Shafi Shah; Hazir Rahman; Raham Sher Khan (Sugar Tech, 2024)

Molecular characterization of Peste des petits ruminants virus (PPRV) in sheep and goats and risk factors associated with it in selected districts of Khyber Pakhtunkhwa-Pakistan - Saira Awaz; Iram Maqsood; Hanif Ur Rahman; Muhammad Ijaz Ali; Baitullah Khan; Gul Muhammad; Imtiaz Ali Shah; Asima Azam; Ayesha Hidayat; Almas Faryal Nizam (Molecular Biology Reports, 2024)

Nanoparticles in plant resistance against bacterial pathogens: current status and future prospects - Maria Gul; Raham Sher Khan; Zia Ul Islam; Sumayya Khan; Amina Shumaila; Sidra Umar; Sajad Khan; Brekhna; Muhammad Zahoor; Allah Ditta (Molecular Biology Reports, 2024)

Biochar and PGPR: A Winning Combination for Peanut Growth and Nodulation under Dry Spell - Tashfeen Alam; Fatima Bibi; Hunaiza Fatima; Faiza Munir; Alvina Gul; Ghulam Haider; Muhammad Jahanzaib; Rabia Amir (Journal of Soil Science and Plant Nutrition, 2024)

Efficient indirect electrochemical degradation of bromothymol blue and methyl red from aqueous phase at Ti/Ru0.3Ti0.7O2 anode - S. Hussain; S. Muhammad; S. Gul; S. Hussain; A. Khan; S. Ahmad; A. Khan (International Journal of Environmental Science and Technology, 2024)

Application of zinc nanoparticles as seed priming agent improves growth and yield of wheat seedlings grown under salinity stress by enhanced antioxidants activities and gas exchange attributes - Sara Zafar; Shahbaz Khan; Danish Ibrar; Muhammad Kamran Khan; Zuhair Hasnain; Kashf Mehmood; Afroz Rais; Safia Gul; Sohail Irshad; Muhammad Nawaz (Cereal Research Communications, 2024)

In vitro and in vivo efficacy of zinc oxide green nanoparticles against multidrug-resistant Salmonella Typhi - Tasbiha Gul; Lubna Tabassam; Abroo Basharat; Afreenish Amir; Zulqarnain Baqar; Muhammad Jawad Khan (Brazilian Journal of Microbiology, 2024)

Bioactivities of natural product geodin congeners and their preliminary structure activity relationship - Gulab Said; Amjad Ali; Muhammad Umair; Farooq Ahmad; Salma Gul; Muhammad Ateeq (Natural Product Research, 2024)

Dietary Chlorella vulgaris mitigates aflatoxin B1 toxicity in broiler chicken: Toxicopathological, hematobiochemical and immunological perspectives - Aisha Khatoon; Aneela Amin; Sana Majeed; Shafia Tehseen Gul; Muhammad Imran Arshad; Muhammad Kashif Saleemi; Ashiq Ali; Rao Zahid Abbas; Sheraz Ahmad Bhatti (Toxicon, 2024)

Cities in the heat: Unveiling the urbanized impacted surface urban heat island of South Korea's metropolises - Muhammad Farhan Ul Moazzam; Sanghyun Kim; Byung Gul Lee (Remote Sensing Applications: Society and Environment, 2024)

Aflatoxin B1-associated oxidative stress along with toxicopathological and immunological alterations is efficiently counteracted by dietary supplementation of distillery yeast sludge in broilers - Aisha Khatoon; Muhammad Zargham Khan; Zain ul Abidin; Muhammad Kashif Saleemi; Halis Oguz; Shafia Tehseen Gul; Rao Zahid Abbas; Ashiq Ali; Sheraz Ahmad Bhatti (Mycotoxin Research, 2024)

Biochar-based adsorption for heavy metal removal in water: a sustainable and cost-effective approach - Jalal Bayar; Nawab Ali; Younsuk Dong; Uzair Ahmad; Muhammad Mehran Anjum; Gul Roz Khan; Muhammad Zaib; Arshad Jalal; Rovaid Ali; Liaqat Ali (Environmental Geochemistry and Health, 2024)

Surviving the desert's grasp: Decipherment phreatophyte Tamarix aphylla (L.) Karst. Adaptive strategies for arid resilience - Ummar Iqbal; Ali Daad; Ahmad Ali; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (Plant Science, 2024)

Legume choice and planting configuration influence intercrop nutrient and yield gains through complementarity and selection effects in legume-based wheat intercropping systems - Muhammad Ali Raza; Atta Mohi Ud Din; Ghulam Abbas Shah; Wang Zhiqi; Ling Yang Feng; Hina Gul; Hassan Shehryar Yasin; Mohammad Shafiq ur Rahman; Chen Juan; Xue Liang; Raheela Rehman; Amal Mohamed Al Garawi; et al. (Agricultural Systems, 2024)

Environmental, technological, and economic analysis of supercritical coal-fired power system - Hamad Hussain Shah; Muhammad Amin; Anaiz Gul Fareed; Muhammad Ali; Francesco Pepe; Piero Bareschino (Environmental Science and Pollution Research, 2024)

Appraisal of Urban Waterlogging and Extent Damage Situation after the Devastating Flood - Shan-e-hyder Soomro; Muhammad Waseem Boota; Xiaotao Shi; Gul-e-Zehra Soomro; Yinghai Li; Muhammad Tayyab; Caihong Hu; Chengshuai Liu; Yuanyang Wang; Junaid Abdul Wahid; Mairaj Hyder Alias Aamir Soomro; Jiali Guo; et al. (Water Resources Management, 2024)

Integrated Application of Micronutrients Improves Productivity and Seed Quality of Canola Crop under Conventional Tillage System - Muhammad Ijaz; Shahbaz Khan; Sami Ul-Allah; Abdul Sattar; Ahmad Sher; Muhammad Nawaz; Amjad Hussain; Afroz Rais; Safia Gul; Danish Ibrar; Manzer H. Siddiqui; Abdel-Rhman Z. Gaafar; et al. (International Journal of Plant Production, 2024)

Optimization of Selenium Inclusion Level in the Larval Diet of Labeo rohita - Shanza Gul; Amina Zuberi; Javeria Shamas; Mashooq Ali; Muhammad Kamran (Biological Trace Element Research, 2024)

Elevation dependent climate assessment and its influence on snow cover variability in Hindu Kush Himalayan region using Google Earth Engine for the period of 2003–2021 - Muhammad Farhan Ul Moazzam; Abhishek Banerjee; Ghani Rahman; Byung Gul Lee (Remote Sensing Applications: Society and Environment, 2024)

Optimization of inclusion level of lipid in larval diet of Labeo rohita (Hamilton, 1822) - Javeria Shamas; Amina Zuberi; Muhammad Aleem Khan; Shanza Gul; Mashooq Ali; Muhammad Kamran (Fish Physiology and Biochemistry, 2024)

ConvEQ: Convolutional neural network for earthquake phase classification using short time frequency transform - Gul Rukh Khattak; Gul Muhammad Khan; Suhail Yousaf (Computers & Geosciences, 2024)

Recent Progress of Fluorescent Carbon Dots and Graphene Quantum Dots for Biosensors: Synthesis of Solution Methods and their Medical Applications - Rafaqat Khan; Amina Qureshi; Muhammad Azhar; Zia Ul Hassan; Sagheer Gul; Saeed Ahmad (Journal of Fluorescence, 2024)

Integrated AI-driven optimization of Fenton process for the treatment of antibiotic sulfamethoxazole: Insights into mechanistic approach - Saima Gul; Sajjad Hussain; Hammad Khan; Muhammad Arshad; Javaid Rabbani Khan; Artur de Jesus Motheo (Chemosphere, 2024)

Sugarcane/soybean intercropping enhances crop productivity, nutrient uptake, and net economic return with reduced inputs - Muhammad Ali Raza; Atta Mohi Ud Din; Hina Gul; Wang Zhiqi; Hassan Shehryar Yasin; Muhammad Hayder Bin Khalid; Nasir Iqbal; Amjad Saeed; Birra Bukhari; Munirah Abdullah Al Dosary; Chen Juan; Xue Liang; et al. (Field Crops Research, 2024)

Electrochemical C-C coupling mediated by novel Sn-SnO2 supported Cu single atoms: The case of CO2 conversion to ethanol - Muhammad Aurang Zeb Gul Sial; Na Guo; Abdul Jalil; Muhammad Abbas; Muhammad Mateen; Sami Ullah; Umair Alam; Zahid Manzoor Bhat; Arshad Hussain; Xingke Cai; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Green synthesis of silver nanoparticles for their antifungal activity against anthracnose disease causing Colletotrichum capsici - Anum Haq Nawaz; Ansar Mehmood; Abd ur Rehman Khalid; Muhammad Abdul Rauf Khan; Gul-e-lala; Khawaja Shafique Ahmad; Asad Ghulam Nabi (Biocatalysis and Agricultural Biotechnology, 2024)

Combined Effect of Biochar and Plant Growth-Promoting Rhizbacteria on Physiological Responses of Canola (Brassica napus L.) Subjected to Drought Stress - Gul-Lalay; Sami Ullah; Sikandar Shah; Aftab Jamal; Muhammad Farhan Saeed; Adil Mihoub; Adil Zia; Iftikhar Ahmed; Mahmoud F. Seleiman; Roberto Mancinelli; Emanuele Radicetti (Journal of Plant Growth Regulation, 2024)
Biochar (BC) and plant growth-promoting microbes (PGPR) could represent a suitable agronomical strategy to mitigate the impacts of drought in arid agro-environmental conditions. However, there is currently little understanding of the synergistic benefit of combining BC and PGPR to increase drought tolerance in oilseeds. In this study, the physiological response of two water-stressed canola ( Brassica napus L.) plants subjected to the application of BC obtained from waste wood of Morus alba applied solely or in combination with PGPR strains ( Pseudomonas sp.) was evaluated. The experiment consists of two genotypes and nine treatments [(C-Control, T1-15 days drought (15DD), T2-30 days drought (30DD), T3-15 days of drought + PG (15DD + PG), T4-30 days of drought + PG (30DD + PG), T5-15 days drought + biochar (15DD + BC), T6-30 days drought + biochar (30DD + BC), T7-15 days drought + biochar + PG (15DD + BC + PG), T8-30 days drought + biochar + PG (30DD + BC + PG)]. Drought stress decreased emergence energy (EE), leaf area index (LAI), leaf area ratio (LAR), root shoot ratio (RSR), moisture content of leaves (MCL), percent moisture content (%MC), moisture content of shoot (MCS) and moisture content of root (MCR), and relative water content (RWC) in both varieties of Brassica napus L., which in contrast, it is increased by the collective application of both biochar and PGPR. In both varieties, N, P, K, Mg, and Ca concentrations were highest in all the biochar and PGPRs separate and combined treatments, while lowest in 15 and 30 days drought treatments. Osmolyte contents like Glycine betaine (GB) and sugar remarkably increased in the stress condition and then reduced due to the synergistic application of biochar and PGPR. Drought stress has a repressive effect on the antioxidant enzymatic system like Peroxidase (POD), Superoxide dismutase (SOD), and glutathione reductase (GR) as well as total flavonoids, phenolics, and protein content. The antioxidant enzymes and phenolic compounds were dramatically increased by the combined action of biochar and PGPRs. A significant increase in EE, LAR, RSR, and RWC under 15 and 30 days drought conditions, evidently highlighting the synergistic effect of BC and PGPR. The results conclude a substantial and positive effect of the combined use of BC and PGPR strains on canola's response to induced drought stress, by regulating the physiological, biochemical, and agronomic traits of the plants. Graphical Abstract

Insect resilience: unraveling responses and adaptations to cold temperatures - Farman Ullah; Arzlan Abbas; Hina Gul; Ali Güncan; Muhammad Hafeez; Basana-Gowda Gadratagi; Lizette Cicero; Ricardo Ramirez-Romero; Nicolas Desneux; Zhihong Li (Journal of Pest Science, 2024)

RETRACTED ARTICLE: Multifaceted role of TRIM21 in inflammation - Sana Tanveer; Ali Afzal; Zaman Gul; Hanan Afzal; Amara Noureen; Muhammad Sharif; Muhammad Babar Khawar (Biologia Futura, 2024)

Current progress and future perspective of microalgae biomass pretreatment using deep eutectic solvents - Gul Muhammad; Jingliang Xu; Zhenglong Li; Ling Zhao; Ximing Zhang (Science of The Total Environment, 2024)

How effective is twitter (X) social media data for urban flood management? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Gul-e-Zehra Soomro; Xiaotao Shi; Jiali Guo; Yinghai Li; Muhammad Tayyab; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Chengshuai Liu; Yuanyang Wang; et al. (Journal of Hydrology, 2024)

Brown macro-seaweeds derived agro-biostimulant for Zea mays farming in saline conditions: Growth enhancement and optimum biochemical and ion feedback - Sadaf Gul; Muhammad Farrakh Nawaz; Muhammad Talha Bin Yousaf; Muhammad Haroon U Rashid; Muhammad Yousuf Adnan; Shamama Tausif; Arooj Javed; Zainul Abideen; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Water requirements of banana and papaya under different water table depths and soil types in the Lower Indus Basin of Pakistan - Nazar Gul; Hafiz Abdul Salam; Muhammad Ashraf (Irrigation and Drainage, 2024)
The water requirements of banana and papaya, the two most important fruit crops of Pakistan, are not known because farmers continue to apply water even if the crop does not need it. In this study, the evapotranspiration (ET), groundwater contribution (GW) and crop coefficient ( K c ) values of banana (1995–1999) and papaya (2013–2016) were determined under different water table depths (WTDs) and soil types using drainage‐type lysimeters. The WTDs were maintained at 1.50, 2.00 and 2.50 m from the ground surface by means of Mariotte bottles. The banana ET during the first year was between 1653 and 1992 mm with a GW contribution of 11–20%, whereas during the second to fifth years, it was between 2430 and 3023 mm with a GW contribution of 10–16%. The banana yield was in the range of 58,638–79,780 kg ha −1 , and the water use efficiency (WUE) was between 2.65 and 3.31 kg m −3 . The papaya ET was between 1478 and 1766 mm with a GW contribution of 7–18% at 1.50–2.50 m WTDs. The papaya yield was in the range of 61,184–83,004 kg ha −1 with a WUE of 4.13–4.70 kg m −3 . Therefore, GW contribution is an important component of the water balance under shallow water table conditions and should be considered when devising irrigation scheduling for banana and papaya crops.

Diversity of melliferous Flora (Apiaries) in Honey and microscopic authentication using LM and SEM Techniques - Khushdil Khan; Khafsa Malik; Mushtaq Ahmad; Rahmatullah Qureshi; Muhammad Asif Aziz; Safia Gul; Wahidah H. Al-Qahtani; Raees Khan (Flora, 2024)

Covalent organic polymers for efficient removal of iodine from gas- and liquid-phase environments - Haishan Zhu; Yuancheng Qin; Yue Guo; Zhen Shen; Muhammad Imran; Muhammad Asim Mushtaq; Zhiqi Zhang; Cailing Ni; Yanqing Chen; Yangbin Ding; Hajera Gul; Jianping Zou; et al. (Chemical Engineering Journal, 2024)

Iron Oxide-Chitosan-Based Nanocomposite for Efficient Fluoride Removal From Drinking Water - Suraya Samejo; Jameel Ahmed Baig; Tasneem Gul Kazi; Hassan Imran Afridi; Saima Perveen; Muhammad Umer Frooq; Khalil Akhtar; Shakoor Ahmed Solangi; Fahad Abbasi; Sajjad Hussain (Water, Air, & Soil Pollution, 2024)

Biological response of red palm weevil (Rhynchophorus ferrugineus, Olivier) (Coleoptera: Curculionidae) on six different varieties of date palm - Gul Rehman; Muhammad Mamoon-ur-Rashid; Habib Ali; Mirza Abdul Qayyum; Shahbaz Ali; Muhammad Ali; Obaid Ullah Sayal; Asif Latif; Asghar Ali Khan (International Journal of Tropical Insect Science, 2024)

Urbanization influenced SUHI Of 41 megacities of the world using big geospatial data assisted with google earth engine - Muhammad Farhan Ul Moazzam; Byung Gul Lee (Sustainable Cities and Society, 2024)

Unravelling the elevation-dependent warming in the Indus Basin - Muhammad Farhan Ul Moazzam; Sudeep Thakuri; Ghani Rahman; Byung Gul Lee (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Genome-wide association study reveals novel genes on different chromosomal positions regulating boll weight in upland cotton (Gossypium hirsutum L.) - Zubair Iqbal; Muhammad Shahid Iqbal; Salman Alamery; Khurram Shehzad; Qamar U. Zaman; Safira Attacha; Zareen Sarfraz; Mian Faisal Nazir; Daowu Hu; Muhammad Mubashar Zafar; Aqib Zeb; Shoupuhe; et al. (Genetic Resources and Crop Evolution, 2024)

Identification and validation of restricted seed color polymorphic sites in Barley (Hordeum vulgare L.) using SNPs derived CAPS markers - Murad Ali; Danish Ibrar; Zuhair Hasnain; Afroz Rais; Shahbaz Khan; Kashf Mehmood; Sami Ullah; Ali Bakhsh; Safia Gul; Muhammad Musawir Khan; Waqar Khan; Muhammad Nisar; et al. (Genetic Resources and Crop Evolution, 2024)

Phytoremediation of heavy metals spiked soil by Celosia argentea L.: effect on plant growth and metal stabilization - Umer Hussain; Rabia Afza; Iram Gul; Muhammad Anwar Sajad; Ghulam Mujtaba Shah; Zahir Muhammad; Shujaul Mulk Khan (Environmental Science and Pollution Research, 2024)

Genotypic variation of tomato to AMF inoculation in improving growth, nutrient uptake, yield, and photosynthetic activity - Fazal Ullah; Habib Ullah; Muhammad Ishfaq; Rahmatullah Khan; Syeda Leeda Gul; Ashrit Gulfraz; Chunwei Wang; Li Zhifang (Symbiosis, 2024)
Arbuscular mycorrhizal fungi (AMF) promote water and mineral nutrients uptake by plant roots, which can reduce the chemical fertilizer inputs in crop production. To gain better insight into the comparative effect of different strains of AMF in improving tomato performance at morphological and physiological levels, seedlings of two tomato cultivars (i.e., Better Boy and Roma) were inoculated with four strains of Glomus mosseae (i.e., HS 1–2 , BEG 12 , BEG 55 , and BEG 54 ) under greenhouse conditions. Results showed that tomato growth and yield varied largely depending on the mycorrhizal strain and tomato cultivar, with wide variations in root colonization ranging from 5.30 to 78.63%. Overall, mycorrhization with BEG 54 showed significantly better tomato performance when compared to the BEG 55, HS 1–2 and BEG 12 strains. In the case of cultivars, Better Boy performed better than Roma cultivar in terms of growth, physiological traits, yield, and fruit quality. The highest plant height, dry matter, nitrogen, phosphorus, potassium, chlorophyll a, chlorophyll b, AMF colonization, yield, fruit juice, ascorbic acid, and titratable acidity contents were recorded in Better Boy cultivar while the highest stem diameter was found in Roma cultivar. Taken together, AMF colonization suggested a promising approach for large-scale tomato production by efficient absorption and utilization of nutrients, and encouraging plants’ symbiotic relationships with soil microorganisms.

Pathological effects of feeding aflatoxin-contaminated feed on immune status and reproductive performance of juvenile white leghorn males and its mitigation with ∝-tocopherol and Moringa oleifera - Muhammad Kashif Saleemi; Ahmad Raza; Aisha Khatoon; Muhammad Zubair; Shafia Tehseen Gul; Xu Yongping; Bilal Murtaza; Faqir Muhammad; Bushra Akhtar; Farhat Jubeen; Farzana Rizvi; Khawar Zubair; et al. (Environmental Science and Pollution Research, 2023)

Unraveling the combined deleterious effects of ochratoxin A and atrazine upon broiler’s health: Toxicopathological, serum biochemical and immunological perspectives - Aisha Khatoon; Muhammad Yasir Nawaz; Ghazala Mehboob; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Rao Zahid Abbas; Muhammad Umar Ijaz; Bilal Murtaza; Sheraz Ahmed Bhatti; Zain ul Abidin; Aamir Riaz Khan (Toxicon, 2023)

Underground geological sequestration of carbon dioxide (CO2) and its effect on possible enhanced gas and oil recovery in a fractured reservoir of Eastern Potwar Basin, Pakistan - Anaiz Gul Fareed; Asif Hussain Khoja; Fabio De Felice; Antonella Petrillo; Muhammad Arsalan Sultan; Zafar Khan Jalalzai; Syed Sheraz Daood (Science of The Total Environment, 2023)

Genome wide identification and expression profiling of PYL genes in barley - Ali Shahzad; Muhammad Shahzad; Muhammad Imran; Hameed Gul; Shareef Gul (Plant Gene, 2023)

Enhanced lead phytoextraction and soil health restoration through exogenous supply of organic ligands: Geochemical modeling” - Maria Manzoor; Muhammad Shafiq; Iram Gul; Usman Rauf Kamboh; Dong-Xing Guan; Abdulrahman Ali Alazba; Sven Tomforde; Muhammad Arshad (Journal of Environmental Management, 2023)

Unraveling the defensive strategies of camel thorn Alhagi maurorum medik. For thriving in arid and semi-arid environments - Ummar Iqbal; Ahmad Ali; Ali Daad; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq; Muhammad Faisal Gul (Journal of Arid Environments, 2023)

Recent advances in microalgae, insects, and cultured meat as sustainable alternative protein sources - Nayab Fatima; Mohammad Naushad Emambux; Amin N. Olaimat; Alexandros Ch Stratakos; Asad Nawaz; Agung Wahyono; Khalid Gul; Jiyong Park; Hafiz Muhammad Shahbaz (Food and Humanity, 2023)

Effect of crop combination on yield performance, nutrient uptake, and land use advantage of cereal/legume intercropping systems - Muhammad Ali Raza; Wang Zhiqi; Hassan Shehryar Yasin; Hina Gul; Ruijun Qin; Sana Ur Rehman; Aqib Mahmood; Zafar Iqbal; Zaheer Ahmed; Shuanglong Luo; Chen Juan; Xue Liang; et al. (Field Crops Research, 2023)

Attenuation of CFA-induced arthritis through regulation of inflammatory cytokines and antioxidant mechanisms by Solanum nigrum L. leaves extracts - Bazgha Gul; Rukhsana Anwar; Mohammad Saleem; Mobasher Ahmad; Muhammad Ihsan Ullah; Shahzad Kamran (Inflammopharmacology, 2023)

Genome-wide identification and expression analysis of U-box gene family in Juglans regia L. - Hanif Khan; Umar Zeb; Sadaf Gul; Azizullah Aziziullah; Naushad Ali; Sajid Fiaz; Asmaa M. Abushady; Shariat Ullah; Salar Muhammad; Kotb A. Attia; Itoh Kimiko; Fengjie Cui; et al. (Genetic Resources and Crop Evolution, 2023)

Geochemical Characterization of Organic Rich Black Rocks of the Niutitang Formation to Reconstruct the Paleoenvironmental Settings during Early Cambrian Period from Xiangxi Area, Western Hunan, China - Rizwan Sarwar Awan; Chenglin Liu; Ashar Khan; Khawaja Hasnain Iltaf; Qibiao Zang; Yuping Wu; Sajjad Ali; Muhammad Amar Gul (Journal of Earth Science, 2023)

Modelling of f o F 2 using artificial neural network over Equatorial Ionization Anomaly (EIA) region stations - Muhammad Ayyaz Ameen; Afnan Tahir; Madeeha Talha; Haqqa Khursheed; Imran A. Siddiqui; Syed Tanweer Iqbal; Bushra Gul (Advances in Space Research, 2023)

Correction to: Overview of environmental and economic viability of activated carbons derived from waste biomass for adsorptive water treatment applications - Hamad Hussain Shah; Muhammad Amin; Francesco Pepe; Erasmo Mancusi; Anaiz Gul Fareed (Environmental Science and Pollution Research, 2023)

Phyto- and bio-management of metal(loid)-contaminated soil by inoculating resistant bacteria: evaluating tolerance of treated rice plant and soil with its efficiency - Zainab Tahir; Muhammad Umar Hayyat; Qaiser Farid Khan; Faiza Sharif; Muhammad Farhan; Laila Shahzad; Gul Zareen Ghafoor (Environmental Science and Pollution Research, 2023)

Overview of environmental and economic viability of activated carbons derived from waste biomass for adsorptive water treatment applications - Hamad Hussain Shah; Muhammad Amin; Francesco Pepe; Erasmo Mancusi; Anaiz Gul Fareed (Environmental Science and Pollution Research, 2023)

DNA base analysis: An effective tool to resolve taxonomic uncertainty and establish phylogenetic relationship in cryptic genotypes of Pyrus (pear), Rosaceae - Muhammad Saeed Akhtar; Shahid Ullah Khan; Ebraheem Abdu Musad Saleh; Said Muhammad; Mohammad Islam; Umber Zaman; Khalil ur Rehman; Gul Nawab; Muhammad Naveed Akhtar; Nabil A. Alhakamy; M.K. Rasha Ibrahim; Ehab A. Abdelrahman (South African Journal of Botany, 2023)

Nanotechnologies for environmental remediation and their ecotoxicological impacts - Mahnoor Ejaz; Alvina Gul; Munir Ozturk; Ahmed Hafeez; Bengu Turkyilmaz Unal; Sami Ullah Jan; Muhammad Taimur Siddique (Environmental Monitoring and Assessment, 2023)

Survival tactics of an endangered species Withania coagulans (Stocks) Dunal to arid environments - Ummar Iqbal; Fahad Ur Rehman; Muhammad Usama Aslam; Muhammad Faisal Gul; Umar Farooq; Amina Ameer; Naila Asghar; Ansar Mehmood; Khawaja Shafique Ahmad (Environmental Monitoring and Assessment, 2023)

Experimental assessment of retrofitted damaged mortarless dry stacked interlocking masonry walls - Saeed Akbar; Akhtar Gul; Inayat Ullah Khan; Muhammad Haseeb; Khan Shahzada; Sajjad Wali Khan; Naveed Ahmad (Soil Dynamics and Earthquake Engineering, 2023)

An improved adaptive neuro-fuzzy inference system for hydrological drought prediction in Algeria - Mohammed Achite; Enes Gul; Nehal Elshaboury; Muhammad Jehanzaib; Babak Mohammadi; Ali Danandeh Mehr (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Speciation of heavy metals and evaluation of their ecological risk impact on salt-affected wetland soil - Muhammad Waris; Jameel Ahmed Baig; Farah Naz Talpur; Tasneem Gul Kazi; Hassan Imran Afridi (Arabian Journal of Geosciences, 2023)

Seaweed-derived bio-stimulant improves growth and salt tolerance of radish varieties under saline conditions - Sadaf Gul; Zainul Abideen; Muhammad Yousuf Adnan; Maria Hanif; Muhammad Farrakh Nawaz; Shumaila; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2023)

The influence of exogenous melatonin and chitosan on secondary metabolites’ production and biological activities of tissue extracts in agitated micro-shoot cultures of Ajuga integrifolia Buch. Ham. ex D.Don - Muhammad Asad Ullah; Faiza Zareen Gul; Gouhar Zaman; Junaid Iqbal; Samantha Drouet; Duangjai Tungmunnithum; Christophe Hano; Bilal Haider Abbasi (Acta Physiologiae Plantarum, 2023)

Insight into crustacean cathepsins: Structure-evolutionary relationships and functional roles in physiological processes - Isma Gul; Muhammad Nadeem Abbas; Saima Kausar; Jili Luo; Xinyue Gao; Yuhang Mu; Wenhui Fan; Honghuan Cui (Fish & Shellfish Immunology, 2023)

Enhanced Degradation of Acid Orange 52 Using a Polyextremophilic Ascomycete in Stirred Tank Bioreactor - Qandeel Laraib; Maryam Shafique; Muhammad Ali Versiani; Khitab Gul; Uroosa Ejaz; Haji Muhammad; Sehar Afshan Naz; Drauzio E. N. Rangel; Alene Alder-Rangel; Kousar Yasmeen; Nusrat Jabeen; Jing Liu; et al. (Water, Air, & Soil Pollution, 2023)

Isolation of Endophytic Fungi from Halophytic Plants and their Identification and Screening for Auxin Production and Other Plant Growth Promoting Traits - Muhammad Ikram; Niaz Ali; Gul Jan; Farzana Gul Jan; Rainaz Pervez; Muhammad Romman; Rimsha Zainab; Humaira Yasmin; Naeem Khan (Journal of Plant Growth Regulation, 2023)

Comparative valuation of the chlorpyrifos, acetamiprid, and lambda-cyhalothrin toxicity and their hematological and histopathological consequences in pigeons - Shumaila Noreen; Ibrar Muhammad Khan; Muhammad Shehzad Khan; Bibi Zarnaab; Iram Gul; Muhammad Zahoor Khan; Waqar Azeem Jadoon; Shehzad Ghayyur; Yong Liu (Environmental Science and Pollution Research, 2023)

“Retraction notice to Carveol ameliorates mercury-induced oxidative stress, neuroinflammation, and neurodegeneration in a mouse brain” NeuroToxicology 92 (2022) 212–226 - Abdullah Alattar; Arooj Mohsin Alvi; Sajid Rashid; Nadia Hussain; Mehreen Gul; Muhammad Ikram; Atif Ali Khan Khalil; Reem Alshaman; Fawad Ali Shah; Shupeng Li; Jingbo Li (NeuroToxicology, 2023)

Estimation of phytoextraction potential of selected halophytes for accumulation of heavy metals from wetland saline soil - Muhammad Waris; Jameel Ahmed Baig; Farah Naz Talpur; Tasneem Gul Kazi; Hassan Imran Afridi; Sadia Shakeel (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Cassia absus-mediated upregulation of IL-4, IL-10 and downregulation of IL-1β, IL-6, TNF- α, NF-κB, IFN-γ in CFA-induced arthritis model - Bazgha Gul; Rukhsana Anwar; Mohammad Saleem; Afifa Noor; Muhammad Ihsan Ullah (Inflammopharmacology, 2023)

Spatio-temporal snow cover change in the early twenty-first century using improved MODIS dataset: a case study of District Hunza, Pakistan - Muhammad Farhan Ul Moazzam; Ghani Rahman; Kokab Saba Ali; Byung Gul Lee (Climate Dynamics, 2023)

Phytotoxic responses of wheat to an imidazolium based ionic liquid in absence and presence of biochar - Taza Gul; Muhammad Mudasar Aslam; Amir Sada Khan; Tahir Iqbal; Faizan Ullah; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Muhammad Saeed Akhtar (Chemosphere, 2023)

Anti-Balamuthia mandrillaris and anti-Naegleria fowleri effects of drugs conjugated with various nanostructures - Ruqaiyyah Siddiqui; Anania Boghossian; Saif S. Alqassim; Muhammad Kawish; Jasra Gul; Tooba Jabri; Muhammad Raza Shah; Naveed Ahmed Khan (Archives of Microbiology, 2023)

Estimation of glacier mass balance using remote sensing and GIS technology in the Hindu Kush region of northern Pakistan - Sidra Bibi; Muhammad Shafique; Neelum Ali; Shahla Nazneen; Liaqat Ali; Siddique Ullah Baig; Rehman Gul (Earth Science Informatics, 2023)

Synthesis and characterization of porous reduced graphene oxide based geopolymeric membrane with titanium dioxide coating for forward osmosis application - Kashif Khan; Muhammad Irfan; Noor Ul Amin; Heqing Jiang; Saeed Gul (Chemosphere, 2023)

Reduction of metronidazole in municipal wastewater and protection of activated sludge system using a novel immobilized Aspergillus tabacinus LZ-M - Xuan Yu; Chunlan Mao; Wenxue Wang; Saurabh Kulshrestha; Peng Zhang; Muhammad Usman; Simin Zong; Mian Gul Hilal; Yitian Fang; Huawen Han; Xiangkai Li (Bioresource Technology, 2023)

Efficient Regeneration in Sugarcane Using Thin Cell Layer (TCL) Culture System - Aneela Iqbal; Raham Sher Khan; Mubarak Ali Khan; Karim Gul; Muhammad Aizaz; Muhammad Usman; Muhammad Arif (Sugar Tech, 2023)

Comparative Genetic Evaluation of Maize Inbred Lines at Seedling and Maturity Stages Under Drought Stress - Ali Shahzad; Hameed Gul; Muhammad Ahsan; Depeng Wang; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Influence of rangeland protection and seasonal grazing on aboveground vegetation, forage quality and weight gain of small ruminants — a study in Thar Desert, Pakistan - Muhammad Islam; Abdul Razzaq; Sawsan Hassan; Muhammad Zubair; Muhammad Waseem Kalroo; Attaullah Khan; Shamim Gul; Sarfraz Ahmad; Barbara Ann Rischkowsky; Mounir Louhaichi (Journal of Mountain Science, 2023)

Insight into microwave-assisted synthesis of the chitosan-MOF composite: Pb(II) adsorption - Humaira Gul Zaman; Lavania Baloo; Shamsul Rahman Kutty; Khalid Aziz; Muhammad Altaf; Aniqa Ashraf; Faissal Aziz (Environmental Science and Pollution Research, 2023)

Occurrence and Distribution of Heavy Metals in Mining Degraded Soil and Medicinal Plants: A Case Study of Pb/Zn Sulfide Terrain Northern Areas, Pakistan - Javed Nawab; Muhammad Idress; Sajid Ullah; Gul Rukh; Rimsha Zainab; Hassan Sher; Junaid Ghani; Sardar Khan; Zahid Ullah; Imran Ahmad; Syed Weqas Ali (Bulletin of Environmental Contamination and Toxicology, 2023)

The alleviation of drought-induced damage to growth and physio-biochemical parameters of Brassica napus L. genotypes using an integrated approach of biochar amendment and PGPR application - Gul Lalay; Abd Ullah; Nadeem Iqbal; Ali Raza; Muhammad Ahsan Asghar; Sami Ullah (Environment, Development and Sustainability, 2022)
Drought is a major abiotic stress, affecting the metabolism, growth, and productivity of plants worldwide. Therefore, this study aimed/hypothesized to investigate the ameliorative effects of biochar and rhizobacteria in drought-damaged Brassica napus L. genotypes. The plants were divided into two groups based on the drought stress employment (15 days and 30 days). Both groups were then treated with PGPR, biochar, and their co-application, and the samples were taken from shoots and roots of both genotypes. Our results revealed that the drought resulted in a substantial decline in total flavonoids, phenolics, proteins, peroxidase (POD), superoxide dismutase (SOD), glutathione reductase (GR) as well as nutrient uptake in shoots and roots of both the studied genotypes. Contrarily, sugar and glycine betaine (GB) contents increased in both shoots and roots under drought stress conditions. However, the plants with co-application of biochar and PGPR showed better improvement of nutrient uptake, leaf relative water content (RWC), and growth parameters compared to drought-stressed, control, and the plants with sole biochar and PGPR application. In addition, the co-application of PGPR and biochar produced higher levels of sugar, proteins, flavonoids, phenolic compounds, and enzymatic activities (POD, SOD, GR, and dehydroascorbate reductase (DHAR)) than those that were not treated with biochar and PGPR or treated solely. Relative to Westar genotype, the Punjab sarson showed higher drought tolerance. In conclusion, we suggest that the co-application of biochar and PGPR can be an effective strategy for overcoming the drought-induced damage in plants. Graphical Abstract

Phytoaccumulation of cadmium by Pelargonium × hortorum — tolerance and metal recovery - Iram Gul; Maria Manzoor; Imran Ahmad; Jean Kallerhoff; Muhammad Arshad (Environmental Science and Pollution Research, 2022)

Leaf Area Regulates the Growth Rates and Seed Yield of Soybean (Glycine max L. Merr.) in Intercropping System - Muhammad Ali Raza; Hina Gul; Ali Hasnain; Muhammad Hayder Bin Khalid; Sajad Hussain; Ghulam Abbas; Waqas Ahmed; Muhammad Jawad Babar; Zaheer Ahmed; Amjad Saeed; Muhammad Umair Riaz; Azeem Iqbal Khan; et al. (International Journal of Plant Production, 2022)

Exploration of solid waste materials for sustainable manufacturing of cementitious composites - Hamayun Khan; Anwar Baig; Mahtab Faisal; Adnan Khan; Kashif Gul; Nauman Ali; Nisar Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Highly selective and sensitive spectrofluorimetric method for determination of cypermethrin in different environmental samples - Mian Muhammad; Sikandar Khan; Gul Rahim; Walaa Alharbi; Khadijah H. Alharbi (Environmental Monitoring and Assessment, 2022)

Bioaccumulation and Health Risk Assessment of Heavy Metal (loid)s in Different Fish Species of Hainan Island, China - Tauseef Ahmad; Sumaira Gul; Muhammad Amjad Khan; Xiaoping Diao; Ashfaq Ahmad; Shakil Ahmad (Thalassas: An International Journal of Marine Sciences, 2022)

Antileishmanial Agents Co-loaded in Transfersomes with Enhanced Macrophage Uptake and Reduced Toxicity - Fatima Zahid; Sibgha Batool; Fakhar ud-Din; Zakir Ali; Muhammad Nabi; Salman Khan; Omer Salman; Gul Majid Khan (AAPS PharmSciTech, 2022)

Comparative low lethal effects of three insecticides on demographical traits and enzyme activity of the Spodoptera exigua (Hübner) - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Zhangqian Wang; Hina Gul; Xiaowei Li; Jun Huang; Junaid Ali Siddiqui; Muhammad Qasim; Rui-Long Wang; Muhammad Imran; Mohammed A. Assiri; et al. (Environmental Science and Pollution Research, 2022)

Pathological effects of graded doses of aflatoxin B1 on the development of the testes in juvenile white leghorn males - Anas Ashraf; Muhammad Kashif Saleemi; Mashkoor Mohsin; Shafia Tehseen Gul; Muhammad Zubair; Faqir Muhammad; Sheraz Ahmed Bhatti; Muhammad Raza Hameed; Muhammad Imran; Hamid Irshad; Iqra Zaheer; Ishtiaq Ahmed; et al. (Environmental Science and Pollution Research, 2022)

Heavy metal remediation and resistance mechanism of Aeromonas , Bacillus , and Pseudomonas : A review - Ali Fakhar; Bushra Gul; Ali Raza Gurmani; Shah Masaud Khan; Shafaqat Ali; Tariq Sultan; Hassan Javed Chaudhary; Mazhar Rafique; Muhammad Rizwan (Critical Reviews in Environmental Science and Technology, 2022)

Sargassum wightii Aqueous Extract Improved Salt Stress Tolerance in Abelmoschus esculentus by Mediating Metabolic and Ionic Rebalance - Zawar Khan; Humaira Gul; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Aziz Ud-Din; Zahoor Ahmad Sajid; Sheza Ayaz Khilji; Aliya Rehman; Asma Tabassum; Zahida Parveen; In-Jung Lee (Frontiers in Marine Science, 2022)
Salinity stress has hindered the growth and yield of crops globally. The demands for inducing salt stress tolerance by natural and biological sources with potent antioxidants and growth-promoting metabolites have been the main focus of the recent era. Therefore, the current research was conducted to extract salt stress tolerance-ameliorating metabolites and growth-promoting hormones from the marine brown macroalgae Sargassum wightii Greville ex J. Agardh with maximum antioxidant potential used as a liquid fertilizer for okra ( Abelmoschus esculentus L.). In the current study, the biochemical analysis showed that Sargassum aqueous extract (SAE) was rich in growth-promoting metabolites, antioxidants, and hormones. Meanwhile, overaccumulation of glycine betaine attracted the focus of the current research dealing with salt stress tolerance amelioration in A. esculentus . The plants supplemented with SAE (2% and 4%) and 0.04% ascorbic acid (AsA) alone and in combinations were subjected to sodium salt stress (NaCl; 75 mM). Results revealed that SAE efficiently promoted the vegetative and reproductive growth of plants by elevating the growth-promoting metabolites and hormones in comparison to control plants. Ionic contents (Na + , K + , Ca 2+ , and Mg 2+ ) and ratios (K + /Na + , Mg 2+ /Na + , and Ca 2+ /Na + ) were modulated in SAE-treated plants. SAE also increased the level of carbohydrates, proteins, lipids, carotenoids, and proline and decreased the level of hydrogen peroxide and abscisic acid in salt-treated plants compared with the control groups. Enzymatic activities of catalase, ascorbate peroxidase, and guaiacol peroxidase were also enhanced by SAE treatment upon salt stress. The SAE-mediated stress tolerance amelioration and the positive growth response of A. esculentus were further accelerated by AsA (0.04%) supplementation used in combination with SAE (2% and 4%). The current study revealed a novel report of the antioxidant and metabolite-rich algal extract ( S. wightii ) formulation along with AsA that induced salt stress tolerance and promoted the overall growth performance of A. esculentus by rebalancing the ionic and metabolic status.

An environmental field assessment of soil quality and phytoremediation of toxic metals from saline soil by selected halophytes - Muhammad Waris; Jameel Ahmed Baig; Farah Naz Talpur; Tasneem Gul Kazi; Hassan Imran Afridi (Journal of Environmental Health Science and Engineering, 2022)

Porostereum spadiceum-AGH786 Regulates the Growth and Metabolites Production in Triticum aestivum L. Under Salt Stress - Syeda Leeda Gul; Yong-Sun Moon; Muhammad Hamayun; Sumera Afzal Khan; Amjad Iqbal; Muhammad Aaqil Khan; Anwar Hussain; Maryam Shafique; Yoon-Ha Kim; Sajid Ali (Current Microbiology, 2022)

Multi-step short-term $$PM_{2.5}$$ forecasting for enactment of proactive environmental regulation strategies - Saba Gul; Gul Muhammad Khan; Sohail Yousaf (Environmental Monitoring and Assessment, 2022)

Endophytic aspergillus oryzae reprograms Abelmoschus esculentus L. to higher growth under salt stress via regulation of physiochemical attributes and antioxidant system - Farzana Gul Jan; Nusrat bibi; Muhammad Hamayun; Yong-Sun Moon; Gul Jan; Maryam Shafique; Sajid Ali (Biologia, 2022)

Erratum to: Impact of rangeland enclosure and seasonal grazing on protected and unprotected rangelands in Chakwal region, Pakistan - Muhammad Islam; Abdul Razzaq; Muhammad Zubair; Sawsan Hassan; Sarfraz Ahmad; Shamim Gul; Barbara Rischkowsky; Mounir Louhaichi (Journal of Mountain Science, 2022)
The article “Impact of rangeland enclosure and seasonal grazing on protected and unprotected rangelands in Chakwal region, Pakistan”, written by ISLAM Muhammad, RAZZAQ Abdul, ZUBAIR Muhammad, HASSAN Sawsan, AHMAD Sarfraz, GUL Shamim, RISCHKOWSKY Barbara and LOUHAICHI Mounir, was originally published electronically on the publisher’s internet portal (currently SpringerLink) on 27 December 2021 without open access. With the author’s decision to opt for open choice the copyright of the article changed in 02/2022 to © The Author(s) 2022. This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons license, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons license and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/ . The original article has been corrected.

Humic acid overcomes salinity barriers and stimulates growth of Urochondra setulosa by altering ion-flux and photochemistry - Sonia Bano; Muhammad Zaheer Ahmed; Zainul Abideen; Muhammad Qasim; Bilquees Gul; Nasir Uddin Khan (Acta Physiologiae Plantarum, 2022)

Comparative seismic performance assessment of RC and RC/ECC hybrid frame structures: a shake table study - Fasih Ahmed Khan; Muhammad Rashid; Sajjad Wali Khan; Muhammad Rizwan; Yasir Irfan Badrashi; Muhammad Fahim; Muhammad Ashraf Tanoli; Wasim Khaliq; Akhtar Gul (Innovative Infrastructure Solutions, 2022)

Bio-diesel production of sunflower through sulphur management in a semi-arid subtropical environment - Athar Mahmood; Masood Iqbal Awan; Sana Sadaf; Ahmed Mukhtar; Xiukang Wang; Sajid Fiaz; Sher Aslam Khan; Habib Ali; Faran Muhammad; Zafar Hayat; Farhana Gul; Shah Fahad (Environmental Science and Pollution Research, 2022)

Synthesis and evaluation of Ca-doped ferrihydrite as a novel adsorbent for the efficient removal of fluoride - Khalil Ahmad; Izaz Ali Shah; Sharafat Ali; Muhammad Tariq Khan; Muhammad Bilal Ahmed Qureshi; Syed Hassan Ali Shah; Asmat Ali; Wajid Rashid; Hifza Nayab Gul (Environmental Science and Pollution Research, 2022)

Impact of rangeland enclosure and seasonal grazing on protected and unprotected rangelands in Chakwal region, Pakistan - Muhammad Islam; Abdul Razzaq; Muhammad Zubair; Sawsan Hassan; Sarfraz Ahmad; Shamim Gul; Barbara Rischkowsky; Mounir Louhaichi (Journal of Mountain Science, 2022)
Scrub rangelands support livestock grazing and provide ecosystem services to their inhabitants. The present study was conducted in Chakwal, an important tract of the Pothwar Plateau, which sustains herds of small domestic and nomadic ruminants. Urbanization and uncontrolled grazing practices have reduced rangeland productivity and increased soil erosion and resulted in poor land conditions. This study assessed the influence of two years of rangeland protection on aboveground vegetation biomass and the chemical composition of plants and aimed to determine the influence of seasonal grazing on the live-weight gain of small ewes. Using the line intercept method, vegetation data from protected and unprotected plots in 2015 and 2016 were collected at two sites, Dhulli and Begal. Vegetation cover was assessed from images using VegMeasure. Results showed that protected study sites displayed higher vegetation biomass (834 and 690 kg ha -1 ) compared to the unprotected study site (477 and 326 kg ha -1 ) during April and August of both years. In the seasonal grazing trial, the experimental ewes that grazed on protected rangelands showed higher live-weight gain (33–63 g day -1 ) compared to live weight of ewes (17–21 g day -1 ) that grazed on unprotected rangelands during the experimental period of 127 days at both sites. The results suggest that the Chakwal rangeland has tremendous potential to improve vegetation productivity but modern livestock management and seasonal grazing practices are needed to improve carrying capacity and livestock productivity.

Homozygosity mapping coupled with whole-exome sequencing and protein modelling identified a novel missense mutation in GUCY2D in a consanguineous Pakistani family with Leber congenital amaurosis - HADIA GUL; ABDUL HALEEM SHAH; RICARDO HARRIPAUL; SUMRA WAJID ABBASI; MUHAMMAD FAHEEM; MUHAMMAD ZUBAIR; MUHAMMAD MUZAMMAL; SAADULLAH KHAN; JOHN B. VINCENT; MUZAMMIL AHMAD KHAN (Journal of Genetics, 2021)

Sublethal concentrations of clothianidin affect fecundity and key demographic parameters of the chive maggot, Bradysia odoriphaga - Hina Gul; Farman Ullah; Muhammad Hafeez; Kaleem Tariq; Nicolas Desneux; Xiwu Gao; Dunlun Song (Ecotoxicology, 2021)

LC–MS/MS-based profiling of bioactive metabolites of endophytic bacteria from Cannabis sativa and their anti-Phytophthora activity - Irum Iqrar; Muhammad Numan; Tariq Khan; Zabta Khan Shinwari; Gul Shad Ali (Antonie van Leeuwenhoek, 2021)

HEC-RAS and GIS-based flood plain mapping: A case study of Narai Drain Peshawar - Awais Salman; Sher Shah Hassan; Gul Daraz Khan; Muhammad Arif Goheer; Aftab Ahmad Khan; Khurram Sheraz (Acta Geophysica, 2021)

RP-HPLC-based phytochemical analysis and diverse pharmacological evaluation of Quercus floribunda Lindl. ex A. Camus nuts extracts - Madiha Ahmed; Muhammad Adil; Ihsan-ul- Haq; Muhammad Khalid Tipu; Muhammad Qasim; Bilquees Gul (Natural Product Research, 2021)

Do inward foreign direct investment and economic development improve local environmental quality: aggregation bias puzzle - Munir Ahmad; Gul Jabeen; Muhammad Irfan; Cem Işık; Abdul Rehman (Environmental Science and Pollution Research, 2021)

In vitro differentiation effect of CCL4-induced liver injured mice serum on bone marrow-derived mesenchymal stem cells toward hepatocytes like cells - Sulaiman Shams; Nazia Imran; Sahib Gul Afridi; Muhammad Ayaz; Atif Ali Khan Khalil; Abdul Nasir (Cell and Tissue Banking, 2021)

Synergistic influence of CuO nanoparticles and spectral lights transforms biomass, antioxidative response, and antioxidants in Brassica nigra - Muhammad Zia; Hira Zafar; Faiza Zarrin Gul; Bilal Haider Abbasi; Zarrin Fatima Rizvi; Abdul Mannan (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Assessment of heavy metal pollution in Brassica plants and their impact on animal health in Punjab, Pakistan - Zafar Iqbal; Farhat Abbas; Muhammad Ibrahim; Tahir Imran Qureshi; Matin Gul; Abid Mahmood (Environmental Science and Pollution Research, 2021)

Levels of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) in municipal waste dumping site, incinerator and brick kiln residues: evaluation for potential risk assessment - Nida Gul; Bushra Khan; Hizbullah Khan; Said Muhammad; Iqbal Ahmad; Nayab Gul (Arabian Journal of Geosciences, 2021)

Development of broad-spectrum and sustainable resistance in cotton against major insects through the combination of Bt and plant lectin genes - Salah ud Din; Saira Azam; Abdul Qayyum Rao; Mohsin Shad; Mukhtar Ahmed; Ambreen Gul; Ayesha Latif; Muhammad Azam Ali; Tayyab Husnain; Ahmad Ali Shahid (Plant Cell Reports, 2021)

Larvicidal potential of different chromatographic fractions of the n-hexane extract of Artemisia scoparia against the vector mosquito Culex quinquefasciatus - Mirza Gul; Muhammad Zahid; Hazrat Ali (International Journal of Tropical Insect Science, 2021)

Delineating Novel Therapeutic Drug and Vaccine Targets for Staphylococcus cornubiensis NW1T Through Computational Analysis - Mohibullah Shah; Samavia Jaan; Batool Fatima; Muhammad Sameem Javed; Adnan Amjad; Asifullah Khan; Sahib Gul Afridi; Umar Nishan; Anwar Iqbal; Haq Nawaz (International Journal of Peptide Research and Therapeutics, 2021)

A research on conventional and modern algorithms for maximum power extraction from wind energy conversion system: a review - Muhammad Zeeshan Malik; Mazhar Hussain Baloch; Mehr Gul; Ghulam Sarwar Kaloi; Sohaib Tahir Chauhdary; Ali Asghar Memon (Environmental Science and Pollution Research, 2021)

Growth regulation of Desmostachya bipinnata by organ-specific biomass, water relations, and ion allocation responses to improve salt resistance - Muhammad Yousuf Adnan; Tabassum Hussain; Muhammad Zaheer Ahmed; Bilquees Gul; M. Ajmal Khan; Brent L. Nielsen (Acta Physiologiae Plantarum, 2021)

Dihydropyrimidones: A ligands urease recognition study and mechanistic insight through in vitro and in silico approach - Farman Ali Khan; Shahbaz Shamim; Nisar Ullah; Muhammad Arif Lodhi; Khalid Mohammed Khan; Kanwal; Farman Ali; Sahib Gul Afridi; Shahnaz Perveen; Ajmal Khan (Medicinal Chemistry Research, 2021)

Lead availability and phytoextraction in the rhizosphere of Pelargonium species - Maria Manzoor; Iram Gul; Aamir Manzoor; Usman Rauf Kamboh; Kiran Hina; Jean Kallerhoff; Muhammad Arshad (Environmental Science and Pollution Research, 2020)

Human health risk assessment of heavy metals in raw milk of buffalo feeding at wastewater-irrigated agricultural farms in Pakistan - Zafar Iqbal; Farhat Abbas; Muhammad Ibrahim; Tahir Imran Qureshi; Matin Gul; Abid Mahmood (Environmental Science and Pollution Research, 2020)

Erratum to: Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
The article Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018, written by Jawaria GUL, Sher MUHAMMAD, LIU Shi-yin, Siddique ULLAH, Shakeel AHMAD, Huma HAYAT and Adnan Ahmad TAHIR, was originally published Online First without Open Access. After publication in volume 17, issue 3, page 572-587, the author decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The original version of this article has been revised due to a retrospective Open Access order.

Multi-functionalized nanocarriers targeting bacterial reservoirs to overcome challenges of multi drug-resistance - Maria Hassan Kiani; Muhammad Imran; Abida Raza; Gul Shahnaz (DARU Journal of Pharmaceutical Sciences, 2020)

Sodium arsenite toxicity on hematology indices and reproductive parameters in Teddy goat bucks and their amelioration with vitamin C - Muhammad Zubair; Maqbool Ahmad; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Mushtaq Ahmad; Christopher Joseph Martyniuk; Qudrat Ullah; Saqib Umar (Environmental Science and Pollution Research, 2020)

Litter decay in rangeland sites with varying history of human disturbance: a study with Hazargangi Chiltan mountain - Imran Khan; Shamim Gul; Sarfraz Ahmad; Gul Bano Rehman; Agha Waqar Yunus; Iram Gul; Imran Ali; Ali Akbar; Muhammad Islam (Journal of Mountain Science, 2020)

Characterization of a novel cotton MYB gene, GhMYB108-like responsive to abiotic stresses - Abid Ullah; Muhammad Tahir Ul Qamar; Mohammad Nisar; Ali Hazrat; Gul Rahim; Aamir Hamid Khan; Kashif Hayat; Saeed Ahmed; Waqar Ali; Aziz khan; Xiyan Yang (Molecular Biology Reports, 2020)

Testing the effect of different insecticides on Myzus persicae (Homoptera: Aphididae) in field mustard (Brassicae campestris L.) Czern for possible consideration in an IPM strategy - Muhammad Shahbaz Khan; Muhammad Faheem Akbar; Amjad Sultan; Muhammad Shoaib Saleem; Chand Gul (International Journal of Tropical Insect Science, 2020)

Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
Glaciers in the northern Pakistan are a distinctive source of freshwater for the irrigation, drinking and industrial water supplies of the people living in those regions and downstream. These glaciers are under a direct global warming impact as indicated in many previous studies. In this study, we estimated the glacier dynamics in terms of Equilibrium Line Altitude (ELA), mass balance and the snout position variation using remote sensing data between 2001 and 2018. Six glaciers, having area ≥ 20 km 2 each, situated in the Chitral region (Hindukush Mountains) were investigated in this study. Digital Elevation Model (DEM) and available cloud-free continuous series of Landsat and Sentinel the entire study area was a retreat of -231 ± 140 m. No obvious relationship was found between the glacier variation trends and the available gauged climatic data possibly due to the presence of debris cover in ablation zones of all the studied glaciers which provides insulation and reduces the immediate climatic effects.

Revealing heterogeneous causal links among financial development, construction industry, energy use, and environmental quality across development levels - Munir Ahmad; Gul Jabeen; Muhammad Khizar Hayat; Rana Ejaz Ali Khan; Shoaib Qamar (Environmental Science and Pollution Research, 2020)

Dynamics of AB-DTPA-extractable Zn in high and low limed calcareous soils amended with biochar and farmyard and poultry manures - Abida Saleem; Dost Muhammad; Mumtaz Khan; Qudrat Ullah Khan; Muhammad Rizwan; Salma Shaheen; Hamza Noor; Shiza Gul; Muhammad Daud Khan; Shafaqat Ali (Arabian Journal of Geosciences, 2020)

Use of crop growth model to simulate the impact of climate change on yield of various wheat cultivars under different agro-environmental conditions in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Ishfaq Ahmed; Muhammad Ashfaq; Dawood Jan; Shah Fahad; Xiuling Li; Depeng Wang; Muhammad Fahad; Muhammad Fayyaz; Syed Attaullah Shah (Arabian Journal of Geosciences, 2020)

Fabrication and Characterization of Thiolated Chitosan Microneedle Patch for Transdermal Delivery of Tacrolimus - Zulcaif Ahmad; Muhammad Imran Khan; Muhammad Irfan Siddique; Hafiz Shoaib Sarwar; Gul Shahnaz; Syed Zajif Hussain; Nadeem Irfan Bukhari; Irshad Hussain; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

Development and Characterization of Bioadhesive Film Embedded with Lignocaine and Calcium Fluoride Nanoparticles - Hira Ghafar; Muhammad Imran Khan; Hafiz Shoaib Sarwar; Samiya Yaqoob; Syed Zajif Hussain; Imran Tariq; Asad Ullah Madni; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

Awareness and current knowledge of epilepsy - Asmat Ullah Khan; Muhammad Akram; Muhammad Daniyal; Naheed Akhter; Muhammad Riaz; Naheed Akhtar; Mohammad Ali Shariati; Fozia Anjum; Samreen Gul Khan; Abida Parveen; Saeed Ahmad (Metabolic Brain Disease, 2020)

Modeling heterogeneous dynamic interactions among energy investment, SO2 emissions and economic performance in regional China - Munir Ahmad; Zhen-Yu Zhao; Muhammad Irfan; Marie Claire Mukeshimana; Abdul Rehman; Gul Jabeen; Heng Li (Environmental Science and Pollution Research, 2020)

Harnessing natural colorants from algal species for fabric dyeing: a sustainable eco-friendly approach for textile processing - Muhammad Azeem; Naeem Iqbal; Riffat Ayesha Mir; Shahid Adeel; Fatima Batool; Ali Ahmad Khan; Sadaf Gul (Journal of Applied Phycology, 2019)

Development and Evaluation of Optimized Thiolated Chitosan Proniosomal Gel Containing Duloxetine for Intranasal Delivery - Maryam khatoon; Muhammad Farhan Sohail; Gul Shahnaz; Fiza ur Rehman; Fakhar-ud-Din; Asim ur Rehman; Naseem Ullah; Umair Amin; Gul Majid Khan; Kifayat Ullah Shah (AAPS PharmSciTech, 2019)

Novel antimicrobial and antioxidative activity by endophytic Penicillium roqueforti and Trichoderma reesei isolated from Solanum surattense - Muhammad Ikram; Niaz Ali; Gul Jan; Muhammad Hamayun; Farzana Gul Jan; Amjad Iqbal (Acta Physiologiae Plantarum, 2019)

Green algae, Cladophora glomerata L.–based natural colorants: dyeing optimization and mordanting for textile processing - Riffat Ayesha Mir; Shahid Adeel; Muhammad Azeem; Fatima Batool; Ali Ahmad Khan; Sadaf Gul; Naeem Iqbal (Journal of Applied Phycology, 2019)

Fungi-assisted phytoextraction of lead: tolerance, plant growth–promoting activities and phytoavailability - Maria Manzoor; Iram Gul; Jean Kallerhoff; Muhammad Arshad (Environmental Science and Pollution Research, 2019)

Recombinant Tk0522, a carbohydrate esterase homologue from Thermococcus kodakarensis, does not require a signal sequence for translocation to periplasmic space in Escherichia coli - Anam Tariq; Alina Gul; Majida A. Muhammad; Naeem Rashid; Masood A Siddiqui (Biologia, 2019)

Comparative effectiveness of organic and inorganic amendments on cadmium bioavailability and uptake by Pelargonium hortorum - Iram Gul; Maria Manzoor; Nosheen Hashim; Khurram Yaqoob; Jean Kallerhoff; Muhammad Arshad (Journal of Soils and Sediments, 2019)

Assessing the socio-economic impact of climate change on wheat production in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Dawood Jan; Muhammad Ashfaq (Environmental Science and Pollution Research, 2019)

Characteristics of pipe corrosion scales in untreated water distribution system and effect on water quality in Peshawar, Pakistan - Dilawar Farhan Shams; Saeed Islam; Baoyou Shi; Waliullah Khan; Buddhika Gunawardana; Maryam Saad; Muhammad Qasim; Haider Ali Javed; Sahib Gul Afridi; Muhammad Naeem; Gul Shahzada Khan (Environmental Science and Pollution Research, 2019)

Ecophysiological response of early stage Albizia lebbeck to cadmium toxicity and biochar addition - Muhammad Talha Bin Yousaf; Muhammad Farrakh Nawaz; Hammad Fayyaz Khawaja; Sadaf Gul; Shafaqat Ali; Irfan Ahmad; Fahd Rasul; Muhammad Rizwan (Arabian Journal of Geosciences, 2019)

Folate-Functionalized Thiomeric Nanoparticles for Enhanced Docetaxel Cytotoxicity and Improved Oral Bioavailability - Muhammad Sajjad; Muhammad Imran Khan; Sara Naveed; Sana Ijaz; Omer Salman Qureshi; Syed Atif Raza; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2019)

Dioxin leaching risk assessment through selected soils by estimating distribution coefficient and breakthrough curves - Nida Gul; Bushra Khan; Hizbullah Khan; Muhammad Israr (Environmental Monitoring and Assessment, 2018)

Plant growth promoting endophytic fungi Asprgillus fumigatus TS1 and Fusarium proliferatum BRL1 produce gibberellins and regulates plant endogenous hormones - Lubna Bilal; Sajjad Asaf; Muhammad Hamayun; Humaira Gul; Amjad Iqbal; Ihsan Ullah; In-Jung Lee; Anwar Hussain (Symbiosis, 2018)

Biodegradable Ingredient-Based Emulgel Loaded with Ketoprofen Nanoparticles - Rabia Gul; Naveed Ahmed; Naseem Ullah; Muhammad Ijaz Khan; Abdelhamid Elaissari; Asim.ur. Rehman (AAPS PharmSciTech, 2018)

Impact of grazing on soil, vegetation and ewe production performances in a semi-arid rangeland - Muhammad Islam; Abdul Razzaq; Shamim Gul; Sarfraz Ahmad; Taj Muhammad; Sawsan Hassan; Barbara Rischkowsky; M. N. M. Ibrahim; Mounir Louhaichi (Journal of Mountain Science, 2018)

Deciphering the growth, organic acid exudations, and ionic homeostasis of Amaranthus viridis L. and Portulaca oleracea L. under lead chloride stress - Muhammad Tariq Javed; Muhammad Sohail Akram; Noman Habib; Kashif Tanwir; Qasim Ali; Nabeel Khan Niazi; Huma Gul; Naeem Iqbal (Environmental Science and Pollution Research, 2018)

Effects of co-composting of farm manure and biochar on plant growth and carbon mineralization in an alkaline soil - Muhammad Farooq Qayyum; Fatima Liaquat; Rabia Abdur Rehman; Mehreen Gul; Muhammad Zafar ul Hye; Muhammad Rizwan; Muhammad Zia ur Rehaman (Environmental Science and Pollution Research, 2017)

Correlation of lithium levels between drinking water obtained from different sources and scalp hair samples of adult male subjects - Shahnawaz Baloch; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Farah Naz Talpur; Muhammad Balal Arain (Environmental Geochemistry and Health, 2017)

Using Landsat images to monitor changes in the snow-covered area of selected glaciers in northern Pakistan - Chaman Gul; Shi-chang Kang; Badar Ghauri; Mateeul Haq; Sher Muhammad; Shaukat Ali (Journal of Mountain Science, 2017)

Antimicrobial and antioxidant activities of a new metabolite from Quercus incana - Farah Gul; Khalid Mohammed Khan; Achyut Adhikari; Salman Zafar; Muhammad Akram; Haroon Khan; Muhammad Saeed (Natural Product Research, 2017)

Molecular genetic analysis of consanguineous families with primary microcephaly identified pathogenic variants in the ASPM gene - MUZAMMIL AHMAD KHAN; CHRISTIAN WINDPASSINGER; MUHAMMAD ZEESHAN ALI; MUHAMMAD ZUBAIR; HADIA GUL; SAFDAR ABBAS; SAADULLAH KHAN; MUHAMMAD BADAR; RAMZI M. MOHAMMAD; ZAFAR NAWAZ (Journal of Genetics, 2017)

Formulation and In Vitro Characterization of Thiolated Buccoadhesive Film of Fluconazole - Kiran Naz; Gul Shahnaz; Naveed Ahmed; Naveeda Akhtar Qureshi; Hafiz Shoaib Sarwar; Muhammad Imran; Gul Majid Khan (AAPS PharmSciTech, 2017)

Correlation of Cadmium and Magnesium in the Blood and Serum Samples of Smokers and Non-Smokers Chronic Leukemia Patients - Noman Khan; Hasan Imran Afridi; Tasneem Gul Kazi; Muhammad Balal Arain; Muhammad Bilal; Asma Akhtar; Mustafa Khan (Biological Trace Element Research, 2017)

Chromium Exposure in the Adult Population, Consuming Different Types of Smokeless Tobacco Products in Pakistan - Asma Akhtar; Hasan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Sadaf Sadia Arain; Jameel Ahmed Baig; Noman Khan; Mustafa Khan; Muhammad Bilal (Biological Trace Element Research, 2017)

Differences in photosynthetic syndromes of four halophytic marsh grasses in Pakistan - Muhammad Moinuddin; Salman Gulzar; Abdul Hameed; Bilquees Gul; M. Ajmal Khan; Gerald E. Edwards (Photosynthesis Research, 2017)

Influence of Metal-Resistant Rhizobacteria on the Growth of Helianthus annuus L. in Cr(VI)-Contaminated Soil - Ali Bahadur; Aftab Afzal; Rizwan Ahmad; Fahad Nasir; Aman Khan; Vishandas Suthar; Gul Jan; Asfa Batool; Muhammad Amir Zia; Muhammad Mahmood-ul-Hassan (Water, Air, & Soil Pollution, 2016)

Vortex-assisted ionic liquid-based dispersive liquid–liquid microextraction for assessment of chromium species in artificial saliva extract of different chewing tobacco products - Asma Akhtar; Tasneem Gul Kazi; Hassan Imran Afridi; Syed Ghulam Musharraf; Farah Naz Talpur; Noman Khan; Muhammad Bilal; Mustafa Khan (Environmental Science and Pollution Research, 2016)

Assessment of Toxic Metal Uptake by Different Vegetables Grown on Soils Amended with Poultry Waste: Risk Assessment - Oan Muhammad Sahito; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Farah Naz Talpur; Shahnawaz Baloch; Nusrat Shahab Memon; Nasreen Gul Kori (Water, Air, & Soil Pollution, 2016)

Early detection of the effects of compaction in forested soils: evidence from selective extraction techniques - Muhammad Farrakh Nawaz; Guilhem Bourrié; Fabienne Trolard; Jacques Ranger; Sadaf Gul; Nabeel Khan Niazi (Journal of Soils and Sediments, 2016)

Uptake and distribution of minerals and heavy metals in commonly grown leafy vegetable species irrigated with sewage water - Sumera Anwar; Muhammad Farrakh Nawaz; Sadaf Gul; Muhammad Rizwan; Shafaqat Ali; Arshaad Kareem (Environmental Monitoring and Assessment, 2016)

Arsenic Exposure in Children through Drinking Water in Different Districts of Sindh, Pakistan - Jameel Ahmed Baig; Tasneem Gul Kazi; Muhammad Ayaz Mustafa; Imam Bakhsh Solangi; Mirza Junaid Mughal; Hassan Imran Afridi (Biological Trace Element Research, 2016)

Simultaneously removal of inorganic arsenic species from stored rainwater in arsenic endemic area by leaves of Tecomella undulata: a multivariate study - Kapil Dev Brahman; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Muhammad Ishaque Abro; Sadaf Sadia Arain; Jamshed Ali; Sumaira Khan (Environmental Science and Pollution Research, 2016)

Banana peel: an effective biosorbent for aflatoxins - Zahid Hussain Shar; Mary T. Fletcher; Gul Amer Sumbal; Syed Tufail Hussain Sherazi; Cindy Giles; Muhammad Iqbal Bhanger; Shafi Muhammad Nizamani (Food Additives & Contaminants: Part A, 2016)

Evaluation of calcium and lead interaction, in addition to their impact on thyroid functions in hyper and hypothyroid patients - Nusrat Shahab Memon; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Sadaf Sadia Arain; Oan Muhammad Sahito; Shahnawaz Baloch; Muhammad Waris (Environmental Science and Pollution Research, 2016)

Comparative Assessment of Synthetic-derived and Conventional Bread Wheat Advanced Lines Under Osmotic Stress and Implications for Molecular Analysis - Ahmad Ali; Muhammad Arshad; S. M. Saqlan Naqvi; Awais Rasheed; Hassan Sher; Alvina Gul Kazi; Abdul Mujeeb-Kazi (Plant Molecular Biology Reporter, 2015)

Causal nexus between energy consumption and carbon dioxide emission for Malaysia using maximum entropy bootstrap approach - Sehrish Gul; Xiang Zou; Che Hashim Hassan; Muhammad Azam; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Correlation of manganese with thyroid function in females having hypo- and hyperthyroid disorders - Nusrat Shahab Memon; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Oan Muhammad Sahito; Shahnawaz Baloch; Muhammad Waris (Biological Trace Element Research, 2015)

An overview of phytochrome: An important light switch and photo-sensory antenna for regulation of vital functioning of plants - Abdul Qayyum Rao; Muhammad Azmat Ullah Khan; Naila Shahid; Salah ud Din; Ambreen Gul; Adnan Muzaffar; Saira Azam; Tahir Rehman Samiullah; Fatima Batool; Ahmad Ali Shahid; Idrees Ahmad Nasir; Tayyab Husnain (Biologia, 2015)

Erratum to: Preconcentration and determination of lead and cadmium levels in blood samples of adolescent workers consuming smokeless tobacco products in Pakistan - Sadaf Sadia Arain; Tasneem Gul Kazi; Hassan Imran Afridi; Kapil Dev Brahman; Naeemullah; Sumaira Khan; Abdul Haleem Panhwar; Muhammad Afzal Kamboh; Jamil R. Memon (Environmental Monitoring and Assessment, 2015)

Combining ability through line × tester analysis for phenological, seed yield, and oil traits in sunflower (Helianthus annuus L.) - Shahnaz Memon; Muhammad Jurial Baloch; Gul Muhammad Baloch; Wajid Ali Jatoi (Euphytica, 2015)

Preconcentration and determination of lead and cadmium levels in blood samples of adolescent workers consuming smokeless tobacco products in Pakistan - Sadaf Sadia Arain; Tasneem Gul Kazi; Hassan Imran Afridi; Kapil Dev Brahman; Naeemullah; Sumaira Khan; Abdul Haleem Panhwar; Muhammad Afzal Kamboh; Jamil R. Memon (Environmental Monitoring and Assessment, 2015)

Comprehensive analysis of CCCH-type zinc finger gene family in citrus (Clementine mandarin) by genome-wide characterization - Shengrui Liu; Muhammad Rehman Gul Khan; Yongping Li; Jinzhi Zhang; Chungen Hu (Molecular Genetics and Genomics, 2014)

Exploitation of synthetic-derived wheats through osmotic stress responses for drought tolerance improvement - Ahmad Ali; Muhammad Arshad; S. M. Saqlan Naqvi; Manzoor Ahmad; Hassan Sher; Sammer Fatima; Alvina Gul Kazi; Awais Rasheed; Abdul Mujeeb-Kazi (Acta Physiologiae Plantarum, 2014)

Genome-Wide Identification, Classification, Expression Profiling, and SSR Marker Development of the MADS-Box Gene Family in Citrus - Xiao-Jin Hou; Sheng-Rui Liu; Muhammad Rehman Gul Khan; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology Reporter, 2014)

Molecular insights to explore abietane diterpenes as new LOX inhibitors - Inamullah Khan; Muhammad Nisar; Armando Zarrelli; Giovanni Di Fabio; Farah Gul; Syed Naeemuddin Gilani; Muhammad Raza Shah; Amir Zada Khan; Samiullah; Hazrat Amin (Medicinal Chemistry Research, 2013)

Determination of toxic elements in different brands of cigarette by atomic absorption spectrometry using ultrasonic assisted acid digestion - Tasneem Gul Kazi; Nusrat Jalbani; Muhammad Balal Arain; Muhammad Khan Jamali; Hassan Imran Afridi; Abdul Qadir Shah (Environmental Monitoring and Assessment, 2009)

Estimation of Toxic Metals in Scalp Hair Samples of Chronic Kidney Patients - Tasneem Gul Kazi; Nusrat Jalbani; Naveed Kazi; Muhammad Balal Arain; Muhammad Khan Jamali; Hassan Imran Afridi; Ghulam Abbas Kandhro; Raja Adil Sarfraz; Abdul Qadir Shah; Rehana Ansari (Biological Trace Element Research, 2009)

Novel mutations in G protein-coupled receptor gene (P2RY5) in families with autosomal recessive hypotrichosis (LAH3) - Zahid Azeem; Musharraf Jelani; Gul Naz; Muhammad Tariq; Naveed Wasif; Syed Kamran-ul-Hassan Naqvi; Muhammad Ayub; Masoom Yasinzai; Muhammad Amin-ud-din; Abdul Wali; Ghazanfar Ali; Muhammad Salman Chishti; et al. (Human Genetics, 2008)

The role of controlled drainage under drought conditions in an irrigated area in NWFP, Pakistan - Gul Daraz Khan; Muhammad Latif; Sibtul Hassan (Irrigation and Drainage, 2003)
The River Swat is the source of irrigation for the entire irrigation system of Mardan, Nowshera and Charsadda districts. Reductions of water and overdrainage have influenced the yield of major crops. The impact of reduced supply at the inlet from the source, drought conditions and overdrainage from the area have lowered the groundwater to a disastrous level. Thus the present groundwater level cannot contribute to the crops. A subsurface collector at its exit in drainage unit 106 was controlled to raise the watertable. The study area was divided into 10 zones. Each zone was separately assessed to analyze the groundwater impact in response to the controlled technique adopted for mitigating drought in different strategies of the canal operation. The interaction of groundwater level with irrigation depth, crop yield, water use efficiency and water saving were also studied. During the rotational period of the canal, irrigations applied in section II raised the water level by nearly 1 m. The upslope area of section III also needed a large irrigation depth. The groundwater level on the downslopes of the lateral drains in sections I and V was at the design depth of 1.1 m during the rotational strategy, while it decreased only slightly on the upslopes of the lateral drains for the same positions. Because of effective control by the collector, the watertable on the downslopes of the laterals in sections II and III was affected less while in the respective upslope area of section III it dropped more than 2 m. The water levels in section IV (both in the upslope and downslope areas along the laterals) remained very close to the design level. A significant contribution of seepage in the upslope of the collector drain considerably reduced the irrigation depths. During the canal closure period, the watertables in the study area dropped to the limit from 2.3 to 3.25 m. After the reopening of the canal, the watertables in sections II, III and IV were raised from 2.55 to 0.70 m. During this period the water levels near the canal reached the design level. The maximum yield of 6.5 tons ha −1 on the downslopes of the lateral drains in section II was obtained, resulting in maximum water use efficiency of 0.93 kg m −3 . However, the minimum yield of 3.5 tons ha −1 on the upslopes of the lateral drains in section I was obtained, resulting in the lowest water use efficiency of 0.35 kg m −3 near the deep surface drain (5 m). The impact of controlled subsurface drainage in zones 2, 3 and 7 resulted in the best maintenance of optimum groundwater level and moisture content. Therefore large amounts of extra irrigation water applied (ranging from 23 to 129% of that actually required) in different zones of the controlled area can be saved for drought conditions. Copyright © 2003 John Wiley & Sons, Ltd.